The calcination mechanism and process optimization of montebrasite and CaSO4/CaCO3/Na2SO4 mixture - Xinyu Zhang; Yao Peng; Lin Zhang; Chongwen Li; Haiyan Wang; Qun Cui (Minerals Engineering, 2026)

EGCG targeting autophagy in cardiovascular diseases: mechanisms and therapeutic potential - Lili Wang; Qizhi Zhang; Si Li; Chunlian Tang; Qun Pan (Molecular Biology Reports, 2026)

Rapid detection of maize seed vigor via multi-branch interpretable deep learning integrated with multimodal data fusion optimized by environmental factors - He Li; Yilin Mao; Ruisha Xie; Hongtao Shi; Han Zhang; Yinlin Chen; Xuelei Yang; Riliang Gu; Sun Qun (Computers and Electronics in Agriculture, 2026)

Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

Contribution of the slab fluids- melts to petrogenesis of adakitic rocks related to gold mineralization: Mo isotopic constraints - Shu-wen Li; Wen-liang Xu; Qun Yang; Yun-sheng Ren; Wu-shuang Zhang; Bin Wang; Kan Gao; Si-tong Chen; Yao-heng Fang; Hao-zhe Li; Tian-ci Liu; Xuan-mei Xue; et al. (Lithos, 2026)

Rhamnolipids: from biosynthesis to applications - Ai-Ping Pang; Zhiqing Zhang; Guo-Zhao Li; Yun Wang; Kun Yang; Junping Zhou; Lianggang Huang; Li-Qun Jin; Zhi-Qiang Liu; Yu-Guo Zheng (Food Chemistry, 2026)

Ultrathin polyacrylonitrile/cellulose nanofiber/hydroxyapatite composite separator regulating desolvation and ion flux for aqueous zinc-ion batteries - Xu-qiao Hu; Li-li Du; Qi-qun Lei; Shuang Zou; Fa-nian Shi; Yu-han Wu; Yu-hang Zhang; Zhe Gong; Peng-fei Wang (Chemical Engineering Journal, 2026)

An integrated strategy for flexible energy storage electrodes from scalable high-loading fabrication to in situ mechanoelectrical evaluation - Xinyu Zhang; Jing Liang; Jia Li; Qun Liu; Panwang Guo; Hehe Ren; Qian Wang; Changzhong Jiang; Vellaisamy A.L. Roy; Wei Wu (Chemical Engineering Journal, 2026)

Direct, catalyst-free H2O2 synthesis via scalable plasma reactor - Dongxing Li; Shao-Pei Wang; Qun Chen; Shengyan Meng; Zhaojun Zhang; Jintao Sun; Shu Liu; Cun-Feng Cheng; Qi Chen; Shui-Ming Hu; Dong H. Zhang; Annemie Bogaerts; et al. (Chemical Engineering Journal, 2026)

Self-powered vibration online monitoring of power transformers enabled by triboelectric nanogenerator - Qun Deng; Shijie Zhai; Xin Yu; Minghao Zhang; Daiyong Yang; Jingyao Luan; Wei Jiang; Xiangzhuang Bi; Hengyu Li; Tinghai Cheng (Chemical Engineering Journal, 2026)

High-efficiency cross-linker TDS enables low-input in vivo structural and interactomic analysis - Beirong Zhang; Yu Xia; Yi Liu; Bowen Zhong; Xiao Li; Yingyun He; Baofeng Zhao; Zhen Liang; Yukui Zhang; Qun Zhao; Lihua Zhang (Analytica Chimica Acta, 2026)

Prevalence and risk factors of bovine tuberculosis in dairy cattle, 2020–2025: A systematic review and meta-analysis of available literature - Qi Wang; Xiao-Nan Wang; Xiao-Qun Liu; Long-Ge Zhao; Zi-Tong Jing; Tian Tian; Jia-Ting Zhang; Yi-Xing Zhao; Jian-Ming Li; Nai-Chao Diao; Kun Shi; Rui Du (Preventive Veterinary Medicine, 2026)

Systematic characterization of the cyclin gene family in the Chinese mitten crab Eriocheir sinensis and functional analysis of representative cyclins in bacteria-induced hemocyte proliferation - Yixi Zhang; Qingding Hao; Chenxiao Que; Xinya Wang; Yang Li; Weiwei Li; Qun Wang; Youting Zhu; Kaimin Zhou (Fish & Shellfish Immunology, 2026)

Triphenyl phosphate exacerbates lung cancer metastasis by activating NF-κB signaling pathway - Shuangshuang Shi; Wenhui Zong; Shengnan Gao; Wenqiu Ding; Yuan Dai; Songtao Liu; Nan Li; Weiping Xie; Hui Kong; Qun Zhang (Environmental Pollution, 2026)

Preparation of amine-grafted spherical silica/cellulose aerogels and investigation of their carbon dioxide adsorption performance - Jingguo Cao; Tengfei He; Xinyu Zhang; Guozheng Sun; Kai Liao; Chengqian Wang; Ke Li; Qun Liu; Yu Zhang (Carbohydrate Polymers, 2026)

Attitude and Heading Calibration After IMU Reinstallation in Rotational Inertial Navigation Systems Using an Interleaved Rotation-Dwell Sequence - Haoyu Bu; Feng Zha; Hongyang He; Jingshu Li; Chenyang Zhang; Qun Zheng (Journal of Marine Science and Engineering, 2026)
To address the degradation in attitude accuracy caused by mismatched rotation-axis tilt parameters after inertial measurement unit (IMU) reinstallation in rotational inertial navigation systems (RINSs) on large marine platforms, an interleaved rotation-dwell attitude-and-heading calibration method is proposed. First, a relative attitude-and-heading model incorporating the combined effects of the rotation-axis tilt errors of the two systems is established, with the horizontal error mapping induced by the relative heading between their base frames explicitly considered. Second, a four-state interleaved rotation-dwell sequence is designed, and the rotation-axis tilt parameters of the two RINSs are separated in closed form through Hadamard orthogonal projection. Simulations verify the parameter-decoupling capability of the proposed method. Experimental results show that, compared to a filtering-based self-calibration method for a single RINS, the proposed method reduces the roll and pitch root-mean-square errors (RMSE) by 90.29% and 41.80%, respectively. After compensation for the rotation-axis tilt errors, relative heading alignment between the two systems is achieved by estimating the residual heading bias. The proposed method provides a system-level solution for attitude-and-heading calibration after IMU reinstallation under moving-base field conditions.

Correlation of hydrophilicity and active N sites with organic iodine adsorption in covalent organic frameworks - Si-Yu Chen; Shuai Wang; Nai-Xin Zhang; Peng-Cheng Zhang; Wei-Qun Shi; Li-Yong Yuan (Journal of Hazardous Materials, 2026)

Dynamic demulsification coupling enhanced mass transfer effect enables efficient and stable oily wastewater separation - Kaili Jin; Ganjunjie Ding; Xiner Zhang; Xinyu Li; Liujun Pei; Hongjuan Zhang; Qun Yang; Shuaitong Liang; Lihui Xu; Jiping Wang (Journal of Environmental Chemical Engineering, 2026)

Fermentation substrate drives flavor differentiation: Multi-omics analysis of flavor formation mechanisms in sour meat fermented by various grains - Jieyu Yang; Ziruo Zhang; Qia Wang; Xin Li; Yingmei Wu; Erhao Zhang; Yingqun Wu; Zhendong Liu; Jingjing Wang; Qun Huang (Food Research International, 2026)

A-site Yb-doped CaMnO3-δ perovskite as a Co-/Sr-free oxygen electrode with enhanced conductivity and stability for solid oxide fuel cells - Qun Yang; Rengang Li; Jingxuan Hao; Hongpeng Fan; Yucheng Zhang; Yue Hu; Xiao Lin; Linjuan Zhang; Dehua Zheng; Zaifeng Li; Jian-Qiang Wang (Chemical Engineering Journal, 2026)

Analysis of Arbuscular Mycorrhizal Fungal Community in Soil of Sugarcane at Different Tillage Depths - Qun-Qing Huang; Sheng Wang; Ying-Jie Nong; Kai-Mao Zhong; Yi-Cheng Su; Xiao-Juan Qin; Jin-Lian Zhang; Yi-Hao Kang; Ting-Su Chen; Shi-Yuan Zeng; Xi-Chao Deng; Ming-Guo Jiang; et al. (Sugar Tech, 2026)

A clinically practical aging clock (physical clock) for healthy aging: development, validation, and application for health assessment and intervention - Xiao-Ming Wang; Jing Pang; Xue Yu; Xuewei Zhang; Shi-Bo Wang; Qi Pan; Aiqun Chen; Lengnan Xu; Nan Li; Xuefei Li; Yao Wang; Yujia Gu; et al. (Science China Life Sciences, 2026)

Effects of in-situ Metaphire guillelmi cultivation combined with straw return on soil microbial dynamics, fertility, and rice productivity in paddy fields - Naling Bai; Chenglong Xu; Weiguang Lv; Shuangxi Li; Xianpu Zhu; Juanqin Zhang; Haiyun Zhang; Xianqing Zheng; Qun Wang; Hanlin Zhang (Plant and Soil, 2026)

An Interpretable Machine Learning Model for Predicting the Presence of Talaromycosis in HIV Patients Lacking Skin Lesions - Jiaguang Hu; Wenming He; Qun Tian; Yanqiu Lu; Peng Zhang; Jinyu Qin; Chuan Qin; Ying Wu; Cheng Huang; Xu Li; Luhuai Feng; Linghua Li; et al. (Mycopathologia, 2026)
Introduction The existing predictive models for talaromycosis in people living with HIV without skin lesions are limited by established risk factors and traditional statistical approaches. This study aims to develop an interpretable machine learning(ML) model for predicting the presence of talaromycosis in HIV patients without skin lesions and to validate its clinical applicability. Methods This retrospective multicenter study involved the analysis of electronic medical records from four tertiary hospitals in China, covering the period from 2010 to 2019. The training dataset comprised 1009 HIV patients with opportunistic infections, while external validation was conducted using data from 305 patients at an independent center. From an initial set of 36 variables, twelve key features were selected, including albumin, absolute lymphocyte count, hemoglobin, alanine aminotransferase (ALT), aspartate aminotransferase (AST), AST/ALT ratio, C-reactive protein, white blood cell count, platelet count, peripheral or abdominal lymphadenopathy, CD4 + T-cell count, and age. Five ML algorithms were evaluated using tenfold cross-validation. Model performance was measured using the AUC, ACC, and F1-score. Calibration curves and decision curve analysis (DCA) were employed to assess the model’s reliability and clinical net benefit. The optimal model was subsequently implemented as a web-based tool. Results The Support Vector Machine (SVM) exhibited superior performance compared to other models, achieving an AUC of 0.809 (95% CI 0.778–0.838), an ACC of 0.714, and an F1-score of 0.689. External validation demonstrated enhanced performance metrics, with an AUC of 0.921 (95% CI 0.889–0.951), ACC of 0.853, and an F1-score of 0.819. DCA indicated a significant net clinical benefit across various risk thresholds, and calibration curves showed strong concordance between predicted and observed risks. Conclusion The interpretable SVM model effectively stratifies the risk of talaromycosis in people living with HIV without skin lesions in endemic regions, aligning with WHO recommendations for early diagnosis and treatment of priority fungal pathogens. Its integration into a web-based tool enhances clinical accessibility for early intervention in resource-constrained settings.

Correction to: Oryzifoliimicrobium ureilyticum gen. nov., sp. nov., a Novel Phosphate‑Solubilizing and Siderophore‑Producing Bacterium Within the Family Rhizobiaceae - Guo‑Hong Liu; Ling Yao; Peng Gao; Shu‑Qun Zhang; Bing Li; Christopher Rensing; Wen‑Qing Li; Shun‑Gui Zhou (Current Microbiology, 2026)

Quantifying the processes governing the seasonality of accelerated Arctic warming - Yupei Zhang; Xiu-Qun Yang; Chenxi Li; Xiaozhuo Sang; Manman Yin (Climate Dynamics, 2026)

Tumor-confined nano-activators for antigen-independent broad activation of tumor-infiltrating T cells - Yue Wang; Min Yang; Bao-Yue Zhang; Mei-Tang Peng; Yi-Qun Sun; Shi-Kun Zhou; Wei Li; Xian-Zhu Yang; Shi-Dang Xu; Zi-Dong Lu; Cong-Fei Xu; Jun Wang (Science Bulletin, 2026)

Homothorax regulates BarH1 expression and olfactory perception in Monochamus alternatus hope - Qi-Cheng Li; Sheng-Xin Wu; Mei-Jiao Yang; Pu-Yuan Zhang; Yan-Ling Wei; Man-Qun Wang (Insect Biochemistry and Molecular Biology, 2026)

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

Highland Barley's future: Processing innovation empowers emerging opportunities in global health foods and sustainable agriculture - Xinlai Dou; Luman Sang; Liangxing Zhao; Yiqing Zhu; Shumin Shu; Yan Zhang; Jing Ou; Hongying Hua; Ge Li; Yong Xue; Qingyu Zhao; Chao Wang; et al. (Trends in Food Science & Technology, 2026)

Deep visual multi-omics reveals intra-tumor heterogeneity of gene expression and immunophenotype in colorectal cancer - Shijun Lei; Wanshan Ning; Hongyan Zhang; Qun Chen; Luming Xu; Shaobo Tian; Xiaoqiong Li; Wenyu Liu; Mengxi Xiang; Feng Liu; Guobin Wang; Lin Wang; et al. (Science Bulletin, 2026)

Identification and functional study of CDK gene family in cell proliferation in the Chinese mitten crab (Eriocheir sinensis) - Wen Zhang; Zifeng Wang; Chaohui Xu; Guoqing Shen; Youting Zhu; Weiwei Li; Qun Wang; Xinpeng Fan (Fish & Shellfish Immunology, 2026)

Corrigendum to “Hellebrigenin induces cell cycle arrest and apoptosis in human hepatocellular carcinoma HepG2 cells through inhibition of Akt” [Chemico. Biol. Interact. 219 (2014) 184-194] - Li-Juan Deng; Li-Ping Hu; Qun-Long Peng; Xiao-Lin Yang; Liang-Liang Bai; Anita Yiu; Yong Li; Hai-Yan Tian; Wen-Cai Ye; Dong-Mei Zhang (Chemico-Biological Interactions, 2026)

Quartz compositions decipher the source and magmatic-hydrothermal evolution of Himalayan LCT-type pegmatites - Yong-Neng Zhao; Jun-Xing Zhao; Noreen J. Evans; Chang-Tong He; Rui-Zhe Shi; Shen Gao; Li-Qun Zhu; Ke-Zhang Qin; Ming-Jian Cao (Mineralium Deposita, 2026)

Microstructure analysis contributes to selection of stem cell-rich explants and identification of embryogenic callus in oil palm tissue culture - Jing Yang; Dongxia Li; Peng Shi; Zhiying Li; Dapeng Zhang; Yin Min Htwe; Qun Yu; Xiangman He; Yong Wang (Plant Biotechnology Reports, 2026)

The expanding world of plant NLR pairs - Cheng-Wei Sang; Yan-Mei Zhang; Sai-Xi Li; Jian-Qun Chen; Zhu-Qing Shao (Trends in Plant Science, 2026)

Atrazine increases hepatic inflammation and injury via endoplasmic reticulum (ER) stress mediated excessive formation of mitochondria-associated membranes (MAMs) and activation of the cGAS-STING pathway - Zi-Jun Sun; Guan-Yue Shan; Hui Wan; Yu-Xin Zhang; Zhi-Cheng Gao; Wen-Na Shi; Lei Lv; Wei-Qun Yan; Hai-Jun Li (Environmental Pollution, 2026)

Efficient construction of triple-phase boundaries for fabrication of high-performance reversible solid oxide cells - Rengang Li; Qun Yang; Jingxuan Hao; Hongpeng Fan; Xiao Wei; Yucheng Zhang; Mingdong Zhou; Xiao Lin; Linjuan Zhang; Jian-Qiang Wang (Chemical Engineering Journal, 2026)

Release of cadmium, lead and zinc from surface soil to the atmosphere via wind erosion at medium-low wind speeds - Qiuye Zhang; Hongyan Liu; Fang Liu; Xuexian Li; Zhe Li; Weijie Chen; Qun Zhao (Atmospheric Pollution Research, 2026)

Targeting methionine-induced pyroptosis enhances anti-tumor immunity - Mingzhu Lei; Wenying Zhu; Chao Wang; Fan Zhang; Miaolin Li; Yi Zhang; Jia Qu; Zhiguo Luo; Jintao Li; Zeng-Xia Li; Miao Yin; Qun-Ying Lei (Science China Life Sciences, 2026)

Investigation on the Mechanical Behavior of Coastal High-Speed Railway Box Girder Under Tsunami Waves - Shaolin Yang; Bohan Yang; Qun Zhang; Zhibin Wen; Kunming Huang; Yuanxun Zheng; Jun Li (Journal of Marine Science and Engineering, 2026)
With the large-scale construction of coastal high-speed railways, understanding the mechanical behavior of high-speed railway box girders under tsunami waves has become increasingly important. Existing studies on tsunami-induced forces on bridge girders have mainly focused on T-girders and plate-girders in highway bridges. In contrast, research on high-speed railway box girders, which are characterized by a significant height-to-width ratio, large cantilevers, and complex ancillary facilities on the girder top, remains relatively scarce, especially regarding its behavior under tsunami waves and the effects of lateral displacement on its dynamic response. In light of this, this study focuses on the investigation of the mechanical behavior of a single-track high-speed railway box girder under tsunami waves, and fifth-order solitary waves and dam-break waves are comparatively employed to simulate the typical unbroken and broken tsunami waves. The interaction between tsunami waves and the fixed railway box girder is numerically conducted, and the characteristics of the interaction process and the variation in maximum forces with girder clearance are thoroughly investigated. After that, the numerical interaction between tsunami waves and the laterally movable railway box girder is comparatively carried out, and the lateral displacement effects on the girder wave forces are exhaustively investigated. The results indicate that unbroken and broken tsunami waves exhibit distinctly different interaction processes with the box girder. With decreasing girder clearance, for the unbroken wave, the maximum horizontal and vertical forces occur when the girder bottom and the cantilever root descend to the initial water surface, respectively; for the broken wave, the horizontal and vertical forces simultaneously occur when the girder bottom nears the water surface with a small clearance. Lateral displacement can reduce wave forces on the girder, but the reduction is quite limited—remaining below 10% at the reference stiffness of an actual bearing. It validates that using a fixed girder model to estimate wave forces on an actual laterally movable girder is a slightly conservative and reasonable approach. This study provides further insight into wave forces acting on coastal high-speed railway box girders in tsunami-prone areas.

Advances in bacterial synthesis pathways of bioflocculants and their applications in mine wastewater treatment - Linlin Zhang; Zhaofeng Liu; Qiang Guo; Jiawei Tang; Xiaoduan Li; Qun Wang (World Journal of Microbiology and Biotechnology, 2026)

Transforming steel slag into a soil-like matrix via CO2 sequestration: A strategy for simultaneous waste valorization and carbon emission reduction - Xin Xie; Chen Li; Zhiyuan Ma; Ludan Zhang; Qun Zhao; Jie Li; Senlin Tian; Kebin He (Journal of Environmental Management, 2026)

Construction of novel porous starch microparticles loaded with curcumin oleogel: Improving colon-targeted delivery potential of curcumin - Li Ma; Dian Liu; Yujia Xu; Qun Liu; Jing Zhou; Chuchu Zhang; Erihemu; Xiaojiang Wu; Liqiang Zou; Wei Liu (Food Chemistry, 2026)

Synergistic optimization of yield, quality, and nitrogen use efficiency in indica rice: Influence of nitrogen management and C-N metabolism linkages - Hongjin Li; Tao Li; Jianghui Yu; Tianyu Du; Ping Zhang; Jingjing Cui; Zheshu Xu; Ying Zhu; Fangfu Xu; Qun Hu; Guodong Liu; Guangyan Li; et al. (Field Crops Research, 2026)

Activation of peroxymonosulfate by MXene-confined micron-sized copper particle catalyst: A new understanding of size effects - Haoran Song; Xudong Zhang; Mengting Guo; Pu Wang; Jie Li; Chen Li; Yan Cao; Linfeng Zhang; Qun Zhao; Xuewei Hu; Senlin Tian (Chemical Engineering Journal, 2026)

Computational-experimental identification of bioactive component combinations from Salvia miltiorrhiza for cardiovascular protection - Yanxia Liu; Jianing Zhang; Zewen Wang; Chaoqun Liu; Shijie Bi; Zhenzhen Xu; Bin Yu; Jiaye Tian; Yue Ren; Qun Li; Xiaoqian Huo; Yanling Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Leaching behavior and toxicity of solid waste from ore-based lithium extraction: Implications for safe storage and resource utilization - Jiefeng Liang; Luqian Zheng; Qun Zhang; Jiawen Yang; Bo Lei; Feigang Yuan; Mingyang Li; Wei Jiang; Yiling Li; Xuezhi Yang; Runzeng Liu; Haiyan Zhang; et al. (Water Research, 2026)

Whole-genome and microbial diversity analyses reveal mechanism of GY8 for enhancing cadmium removal rate of duckweed - Mi Zhang; Yu-Ting Liu; Xiang-Qin Li; Zhi-Qun Chen; Yan Lan; Ai-Juan Tan; Gui-Li Yang (International Biodeterioration & Biodegradation, 2026)

Effect of structural characteristics of highland barley β-glucan by various thermal processing methods on intestinal microbial community and fermentative products - Rong Li; Ji Gao; Yiyun Zhang; Zijian Dai; Siqi Li; Tong Wu; Jiaqian Cao; Kefan Wei; Chao Wang; Qun Shen; Yong Xue (Food Bioscience, 2026)

Bx7 and By8 glutenin subunits dictate freeze-thaw stability in Chinese steam bun dough: Molecular basis across wheat cultivars - Sameh Sharafeldin; Toheed Akbar; Lina Li; Lizhu Cui; Biao Xue; Xiaoyun Zhao; Mahmoud Naser; Samir Mowafy; Zhang Xinyu; Liyuan Qin; Chongyi Wu; Qun Shen (Food Hydrocolloids, 2026)

DSSAT-PSO coupling-driven intelligent optimization for regional nitrogen management: Sequence module refinement and development - Jian-Ning Liao; Bin Wang; Xiu-Fang Zhang; Qun Wu; Li-Yao Zhou; Yu-Lai Ding (Field Crops Research, 2026)

The relationships between the main root morphological characteristics and biomass allocation of Ageratina adenophora along the Qionghai lakeside, western Sichuan Plateau, China - Qun Li; Yu-Mei Qiu; Lan Chen; Cheng-Zhang Zhao; Bo Li; Hong Yang (Plant and Soil, 2026)

Direct and indirect somatic embryogenesis pathways of in vitro propagation via immature inflorescence of coconut and oil palm - Vona Douglas Odenore; Zhiying Li; Peng Shi; Dapeng Zhang; Yin Min Htwe; Qun Yu; Xiangman He; Yong Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Study on the discovery of lung-descending herbs and bioactive constituents using TRP channel-functionalized screening - Bin Yu; Jiaye Tian; Zewen Wang; Liansheng Qiao; Yanxia Liu; Qun Li; Yue Ren; Yuezhong Zhu; Li Lin; Yanling Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Intrinsic capacity across the adult lifespan in China: baseline analysis from the nationwide longitudinal PENG ZU cohort - Ju Cui; Yujia Gu; Jing Pang; Huafang Gao; Li-Qun Zhang; Xiaolan Wu; Junwu Dang; Juan Li; Xinyi Zhu; Senlin Luo; Zhao Wang; Fuyi Tu; et al. (GeroScience, 2026)

Screening of quorum Sensing-Dependent strong promoters in Pseudomonas bijieensis 2P24 for metabolic optimization and Recombinant protein production - Jie Li; Hongguang Ma; Na Tai; Yue Fan; Mengxue Nie; Xuanying Tao; Zhilin Wang; Jinxin Wang; Xiangpeng Deng; Cheng Shen; Xuanxuan Chen; Jin Wang; et al. (World Journal of Microbiology and Biotechnology, 2026)

Chronic social defeat stress accelerates lung cancer progression and induces hippocampal metabolic dysregulation in a duration-optimized comorbid model - Xiao-yu Liu; Shuo Wang; Yu-long Li; Jia Lu; Zheng Zhang; Jia-bin Zheng; Li-qun Jia (Metabolic Brain Disease, 2026)

SnRK2.5-mediated phosphorylation of PIN2 links osmotic stress signaling to auxin-dependent root adaptive growth in Arabidopsis - Shujuan Zhang; Zilong Cui; Yu Gao; Qi Liao; Wenyan Li; Siqi Yuan; Zhuomeng Li; Xinwen Zhang; Kai Ding; Wenjing Zhang; Like Shen; Jörg Kudla; et al. (Molecular Plant, 2026)

Decarbonizing fossil-to-chemicals conversion: reliable real-time optimization under coupled chemical and carbon capture dynamics - Zhibo Zhang; Ze Li; Mengzhen Zhu; Yani Wang; Yibo Yuan; Honghua Qin; Jiarong Lu; Yaqian Li; Xin Zhou; Yibin Liu; Qun Zhang; Hao Yan; et al. (Journal of Cleaner Production, 2026)

Corrigendum to “Non-lytic nanozyme hydrogel for the treatment of fungal keratitis by silent pathogen eradication and host inflammation suppression” [Chem. Eng. J. 527 (2026) 171844/ CEJ_171844] - Na Li; Xia Qi; Li Ma; Xiaoyu Zhang; Yuxin Liu; Shijiu Chen; Fengmei Shan; Qun Wang; Qingjun Zhou; Ting Wang; Hongwei Wang; Weiyun Shi (Chemical Engineering Journal, 2026)

Catalytic co-pyrolysis of rice straw and polystyrene for selective production of monocyclic aromatic hydrocarbons - Na Guo; Zhiwei Wang; Ruijie Liu; Huina Zhu; Gaofeng Chen; Xueqin Li; Qun Wang; Hongxun Zhang; Tingzhou Lei (Process Safety and Environmental Protection, 2026)

Machine learning-driven screening of characteristic flavor compounds: Investigating the impact of ultra-high pressure treatment on the flavor of Tibetan chicken soup - Kai Dong; Xinyuan Huang; Yingmei Wu; Guofeng Jin; Yufang Guan; Hongbo Song; Fengping An; Xin Li; Erhao Zhang; Qun Huang (Food Research International, 2026)

N-doped biochar as a promising peracetic acid activator for sulfamethoxazole removal: Performance and mechanism - Zhuoran Li; Lu Han; Ran Wang; Jiaxuan Yu; Siqi Wang; Kaige Li; Qun Jiang; Jie Liu; Jianhua Qu; Ying Zhang (Chemical Engineering Journal, 2026)

Non-lytic nanozyme hydrogel for the treatment of fungal keratitis by silent pathogen eradication and host inflammation suppression - Na Li; Xia Qi; Li Ma; Xiaoyu Zhang; Yuxin Liu; Shijiu Chen; Fengmei Shan; Qun Wang; Qingjun Zhou; Ting Wang; Hongwei Wang; Weiyun Shi (Chemical Engineering Journal, 2026)

The Reorganization of Cerebellar Functional Network Topology in Post-stroke Aphasia: A Resting-State fMRI Study - Liting Chen; Zhenye Luo; Wenfeng Mai; Xiaoling Wu; Xiaole Fan; Lifeng Li; Yongqiang Shu; Xiaoyun Chen; Qun Fang; Hong Wang; Yanhong Dai; Shuixing Zhang (Molecular Neurobiology, 2026)

Soil bacteria are more sensitive than fungi across different post-fire succession stages: Harnessing microbial sensitivity thresholds for recovery in warm temperate forests - Qing Zhang; Chunyu Zhang; Li Xiu; Bingchu Liu; Zhiqiang Wang; Linqian Yu; Qun Gao; Renqing Wang; Hui Wang; Peiming Zheng (Applied Soil Ecology, 2026)

Characterization and phylogenetic analysis of the mitochondrial genome of Amatitlania nigrofasciata (Günther, 1867) - Li-Luan Lin; Gui-Feng Wei; Qun Zhang (Journal of Genetics, 2025)

Aggregate size mediates the stability and temperature sensitivity of soil organic carbon in response to decadal biochar and straw amendments - Yalan Chen; Yakov Kuzyakov; Qiwen Ma; Zhangliu Du; Ke Sun; Keqing Xiao; Xinru Liang; Yang Li; Yunxian Zhang; Xianqiang Lai; Wei Fu; Bo Gao; et al. (Soil Biology and Biochemistry, 2025)

Water in the lower mantle: constraints from mineral physics and phase equilibrium data - Li Zhang; Qun-ke Xia (Physics of the Earth and Planetary Interiors, 2025)

Coupled deep electrical resistance heating and shallow permanganate oxidation for indoor remediation of chlorinated hydrocarbons in layered soils - Yutian Chen; Xiang Wang; Qun Li; Yuanchao Zhao; Tingting Fan; Junzeng Xu; Shengtian Zhang; Decheng Jin; Jinzhong Wan (Journal of Environmental Chemical Engineering, 2025)

Evolution of water-soluble organic aerosol composition from clean days to haze episodes in rural area of North China Plain - Chun Chen; Long Jia; Zhiqiang Zhang; Jian Gao; Yanmei Qiu; Junling Li; Rui Gao; Ping Li; Qun Zhang; Zhijie Li; Jiaxing Sun; Nan Ma; et al. (Journal of Environmental Sciences, 2025)

Synergistic construction of high-performance oil-in-water emulsions by egg white protein-whey protein isolate dual-protein: achieving efficient utilization of bioactive substances - Yanli Wang; Yuanyuan Zhang; Erjiao Li; Haobo Jin; Yaqin Yang; Sadaqat Ali; Qun Lu; Zhaoxia Cai; Guofeng Jin; Long Sheng (Food Research International, 2025)

Exogenous GABA increases the accumulation of bioactive compounds in broccoli sprouts under NaCl stress by modulating their biosynthesis and gene expression - Ziqi Wang; Zhiyi Zhou; Hao Xu; Weiwei He; Qun Fu; Yihong Bao; Dajing Li; Zhongyuan Zhang; Cunshan Zhou (Food Bioscience, 2025)

Water-resistant and antibacterial food packaging films prepared from bamboo shoot shell cellulose nanofibers and cinnamaldehyde/chitosan emulsion - Lianying Dai; Qun Liu; Meng Li; Xialing Wu; Wenhui Zheng; Wuyin Weng; Yucang Zhang (Food Hydrocolloids, 2025)

A comparative study highlights superiority of LSTM in crop genomic prediction - Ruiqing Pan; Yaolong Yang; Yuanyuan Zhang; Qun Xu; Yue Feng; Junyu Chen; Wei Li; Shoupu He; Xinghua Wei; Mengchen Zhang (Planta, 2025)

Enhanced bioremediation of α-terpineol-contaminated mining soil through immobilization of Indigenous biosurfactant-producing bacteria on biochar - Jin-Cheng Ye; Wei-Liang Li; You-Qun Xie; Huan Du; Lei Xiang; Bai-Lin Liu; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Miaoyue Zhang; Ce-Hui Mo; Hai-Ming Zhao (Biology and Fertility of Soils, 2025)

Differential response patterns of bacterial communities in seawater and sediments to the Chaetomorpha valida bloom in sea cucumber Apostichopus japonicus aquaculture ponds - Hongxia Zhang; Kexin Xu; Ronglian Xing; Linqian Wang; Renyu Liu; Xin Wang; Lihong Chen; Rui Li; Zhen Yu; Xuebin Cao; Cao Cheng; Qun Su (Marine Pollution Bulletin, 2025)

Unraveling ozone formation sensitivity to ambient VOCs and NOx at urban and mountain sites in a typical city of eastern China - Xiaorong Zhang; Deming Han; Jiandong Shen; Feng Chen; Liuyan Cao; Jinhan Chen; Xu Lin; Yang Yang; Lin Yang; Wenjing Li; Xiaowei Qiao; Shuangxu Zhou; et al. (Environmental Pollution, 2025)

Analysis and optimization of a quasi-zero-stiffness vibration isolator based on partially rigidized compliant mechanisms - Zhi-Qiang Zhang; Mu-Qing Niu; Li-Qun Chen (Engineering Structures, 2025)

A general pyrolysis strategy to construct rare-earth oxide-stabilized high-density Ru single atom catalysts for efficient thermocatalytic CO2 methanation - Yunxiang Tang; Yanan Zhang; Aihuan Sun; Hao Wang; Yawei Miao; Zhengyi Yang; Yunqian Tang; Qun Li; Shujiao Wang; Lingheng Kong; Yinfeng Han (Chemical Engineering Journal, 2025)

Nearly 100% selective hydrolysis of pyrolytic sugar over sustainable carbon catalysts enables highly efficient production of bioethanol - Hong-li Ma; Ming-fu Li; Ying-chuan Zhang; Qing-hua Huang; Li-qun Jiang; Zhen Fang (Bioresource Technology, 2025)

Study on the effect of summer classroom temperature on cognitive performance and heart rate variability in elementary school students - Yuerong Li; Qun Zhang; Peng Wang; Yanyan Li; Jiao Yang; Shiliang Wang (Building and Environment, 2025)

Research on Magnetic Z-component Anomalies and Probabilistic Time Series Prediction Based on High-Density Geomagnetic Data in Southwest Yunnan - Lu-Qiang Sun; Tian Song; Chao-Qun Ma; Yan-Li Liu; Ming-Dong Zhang (Applied Geophysics, 2025)

ZWINT down-regulated by miR-495-3p inhibited lung metastasis of breast cancer by blocking p38 MAPK signaling pathway activation - Ming-tao Shao; Wei-wen Li; Yong Li; Ping Chen; Shuai-shuai Yu; Wen-jie Lu; Chun-mei Chen; Yan Dong; Yi-wen Zhang; Qun-chen Zhang (Human Cell, 2025)
Breast cancer metastasis is the primary cause of patient mortality, yet effective therapeutic targets remain limited. Building on our prior identification of ZWINT as a prognostic marker linked to metastasis, this study defines its critical functional role and regulatory mechanism. Multi-omics analysis revealed a strong association between ZWINT expression and metastatic processes across breast cancer subtypes. Functionally, ZWINT knockdown significantly inhibited breast cancer cell migration and invasion in vitro and dramatically reduced lung metastasis in vivo. Mechanistically, we discovered that miR-495-3p directly targets and suppresses ZWINT expression, and this miR-495-3p/ZWINT axis acts through inhibiting p38 MAPK pathway activation to suppress metastatic progression in vitro. Our findings demonstrate that ZWINT drives breast cancer metastasis and is negatively regulated by miR-495-3p. The newly identified miR-495-3p/ZWINT/p38 MAPK axis may provide a promising therapeutic target for suppressing breast cancer progression.

Ichnology across the Permian–Triassic transition at the Meishan section, with implications for palaeoceanic redox evolution in South China - Yi Ding; Li-Jun Zhang; Chang-Qun Cao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Copper pyrithione exposure-induced copper accumulation compromises mouse oocyte maturation - Sheng-Ji Yang; Ming Liu; Yin-Qing Li; Yong-Sheng Wang; Ze-Qun Duan; Jing-Jing Wang; Hai-Miao Lv; Shou-Xin Zhang; Li-Jun Huo (Journal of Environmental Management, 2025)

Enhanced denitrification by bio-cathodes in the treatment of aquaculture wastewater in microbial electrochemical systems - Qun Li; Sirapat Khodseewong; Boyang Chen; Takashi Sakamaki; Haochi Zhang; Xian Cao (Journal of Environmental Chemical Engineering, 2025)

Chalcophile elements in post-subduction magmas and implications for metal recycling in oceanic and continental subduction - Xiang Wang; Zaicong Wang; Li-Qun Dai; Wen Zhang; Xiaodong Deng; Xi Zhang; Stephen Foley; Charles H. Langmuir; Wei Fang; Lang Wang; Tao He; Aiqing Ren; et al. (Geochimica et Cosmochimica Acta, 2025)

A ratiometric fluorescent probe for sensitive detection of benzoyl peroxide and hypochlorite in food - Shun-Qiang Cui; Xin-Yi Liang; Zhi-Qiang Cai; Hou-Qun Yuan; Qiu-Yu Zhang; Yi-Fan Xia; A.K.I.M.A.N.A. Sandra; Ling-Yi Guo; Ran Wang; Shi-Yu Zhao; Yan-Xia Li; Guang-Ming Bao (Food Chemistry, 2025)

DPP-IV inhibitory peptides from highland barley via machine learning and multi-scale validation - Xin Bao; Yiyun Zhang; Liyang Wang; Zijian Dai; Rong Li; Kefan Wei; Jiaqian Cao; Qingyu Zhao; Qun Shen; Yong Xue (Food Chemistry, 2025)

Aptamer-anchored hydrophobic nanopores for electrochemical/fluorescent dual-mode identification of pathogenic bacteria - Jiangxue Dong; Tianyi Lu; Yufan Zhang; Ming Su; Jingjing Wang; Yajie Fan; Yanlei Li; Hongyuan Yan; Shigang Shen; Qun Ma; Zhongfeng Gao (Chemical Engineering Journal, 2025)

Hollow mesoporous silica nanoparticles for enhanced immune protection in a multi-epitope vaccine against pseudorabies virus - Qun Wang; Jian-Dong Zhang; Hong-Xia Hu; Ying-Lei Zhang; Zhen Cheng; Shuang-Yan Xiao; Han Feng; Lin-Tao Li; Jing-Song Liu; Qi Su; Huan-Chun Chen; Zheng-Fei Liu (Chemical Engineering Journal, 2025)

Evolution of MJO structures during eastward propagation - Yuqing Long; Jian Ling; Chongyin Li; Guiwan Chen; Guanshun Zhang; Qun Tian; Lina Huang; Yu Zhu (Theoretical and Applied Climatology, 2025)

Invasion legacy weakens the positive effect of plant genotype diversity on soil multifunctionality - Wei Song; Cai Cheng; Zekang Liu; Shumeng He; Shenggui Xue; Xue Chen; Jingru Zhang; Lejie Wu; Qun Zhang; Guiyao Zhou; Yann Hautier; Ruiting Ju; et al. (Plant and Soil, 2025)

Mitochondrial GPATs protect Arabidopsis from water stress by impacting cuticle and secondary cell wall development - Qianru Jia; Yang Bai; Shujuan Zhang; Li Song; Hongmei Zhang; Wei Zhang; Qiong Wang; Xiaoqing Liu; Xin Chen; Qun Zhang; Huatao Chen (Plant Cell Reports, 2025)

Rapid detection of carbapenem resistance via MALDI-TOF MS using an innovative broth microgrowth assay - Zhenghua Xie; Qun Wang; Ziyuan Zhou; Weixing Wu; Xiaoyu Zhang; Li Zhang (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Advancing NSCLC Diagnosis: The Role of Tumor-Derived Serum Exosomal SNORD60 as a Novel Biomarker - Lin Li; Kangyu Wang; Ning Yuan; Qun Zhang; Xinmei Liang; Zhijun Zhang (Indian Journal of Clinical Biochemistry, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Efficacy and safety of an mRNA encoding neutralizing antibody against SARS-CoV-2 in non-human primates - Hang Chi; Suo-Qun Zhao; Yun-Peng Liu; Xiao-Chuan Xiong; Xia Zhong; Xing-Xing Suo; Xing-Yao Huang; Can Yue; Jing-Jing Zhang; Zhe Cong; Na Li; Fei-Xue Du; et al. (Science Bulletin, 2025)

Heavy metal pollution in aquatic systems of the Hunhe River Basin, China: Source apportionment, ecological and health risk assessments - Haijian Xie; Mengcheng Zhang; Yanghui Shi; Yanhao Wu; Mei Li; Qun Li; Yuanchao Zhao; Jing Hua (Process Safety and Environmental Protection, 2025)

Efficient and complete biodegradation of Poly (butylene adipate-co-terephthalate) by a novel dual-member bacterial consortium from compost: Metabolic division of labor between BDP053 and BDT04 - Qianqian Liu; Xinguo zhang; Junfei Gao; Songhong Fan; Wei Li; Wenli Li; Weidong Liu; Jinshan Li; Qun Gu (Journal of Hazardous Materials, 2025)

Co-Exposure of airborne microplastics and chromium: Impairment of pulmonary surfactant monolayer - Linfeng Zhang; Yan Cao; Jie Li; Chao Li; Yanlin Yang; Jiao Li; Xuewei Hu; Xiangfen Cui; Qun Zhao; Haoran Song; Jianhong Huang; Senlin Tian (Journal of Hazardous Materials, 2025)

An investigation into adsorption process of biologically- fermented semaglutide precursor peptide on macroporous resins - Zhewei Zhang; Ruopeng Li; Lin Zhang; Zhengfei Ma; Haiyan Wang; Qun Cui (Food and Bioproducts Processing, 2025)

A novel multimodal computer-aided diagnostic model for pulmonary embolism based on hybrid transformer-CNN and tabular transformer - Wei Zhang; Yu Gu; Hao Ma; Lidong Yang; Baohua Zhang; Jing Wang; Meng Chen; Xiaoqi Lu; Jianjun Li; Xin Liu; Dahua Yu; Ying Zhao; et al. (Physical and Engineering Sciences in Medicine, 2025)

Oryzifoliimicrobium ureilyticus gen. nov., sp. nov., a Novel Phosphate-Solubilizing and Siderophore-Producing Bacterium Within the Family Rhizobiaceae - Guo-Hong Liu; Ling Yao; Peng Gao; Shu-Qun Zhang; Bing Li; Christopher Rensing; Wen-Qing Li; Shun-Gui Zhou (Current Microbiology, 2025)

Xylem hydraulic impairment due to stronger drought stress accounts for the reduced crown vitality and growth performance of Mongolian pine trees in higher-density plantations - Xue-Wei Gong; Yi-Lei Ouyang; Yan-Yan Liu; Jin-En Zhang; Zhao-Kui Li; Hong-Li Li; Zhuo-Qun Fang; Yu Cao; De-Dong Wu; Qiu-Rui Ning; Guang-You Hao (Agricultural and Forest Meteorology, 2025)

Assessing the stock recovery of Coilia nasus in the Yangtze River-Poyang Lake waterway and adjacent waters, using the length-based Bayesian biomass method - Yulan Luo; Qun Xu; Sheng Wang; Zhengli Luo; Chiping Kong; Legen Peng; Bao Zhang; Baolong Bao; Lekang Li; Xiaoling Gong (Frontiers in Marine Science, 2025)
The comprehensive ten-year fishing ban implemented in the Yangtze River on January 1, 2021, represents a critical ecological conservation measure and national strategic priority in China. Assessment of the ban’s effectiveness is essential to guide future long-term conservation efforts. This study systematically analyzed changes in the stock structure and biomass dynamics of Coilia nasus in the Yangtze River-Poyang Lake waterway and adjacent waters from 2019 to 2024 using the Length-Based Bayesian Biomass (LBB) method. Results showed a notable improvement in age structure, with the proportion of four-year-old individuals increasing from 3.2% in 2020 to 17.2% in 2024, effectively reversing the previous trend toward younger, smaller fish. The average body length and weight increased significantly, from 271.20 ± 38.44 mm, 68.52 ± 33.26 g in 2019 to 305.53 ± 37.99 mm, 88.02 ± 32.01 g in 2024 ( P < 0.05). The dominant size classes shifted step by step, from 250 – 260 mm, 50 – 60 g in 2019 to 330 – 340 mm, 120 – 130 g in 2024. According to the LBB model, the relative biomass ( B/B 0 ) increased from 0.17 to 0.68, and biomass relative to the maximum sustainable yield ( B/Bmsy ) rose from 0.48 to 1.9, demonstrating a transition in the stock status from “outside of safe biological limits” to “healthy” from 2019 to 2024. These trends, along with increases in the Lmean/Lopt , Lc/Lcopt ratios and other indexes, highlight improvements in size structure and a greater presence of larger individuals. In addition, the fishing mortality to natural mortality ratio ( F/M ) markedly declined from 2.6 in 2019 to 0.37 in 2024, underscoring the substantial alleviation of fishing pressure under the ban. To further validate these findings, SPR was estimated using the LBSPR model, increasing from 0.19 to 0.42 and suggesting improved reproductive sustainability. These findings provide strong evidence that the fishing ban has played a critical role in the stock recovery of C. nasus and mitigating the effects of overfishing.

An Assessment of the Population Structure and Stock Dynamics of Megalobrama skolkovii During the Early Phase of the Fishing Ban in the Poyang Lake Basin - Xinwen Huang; Qun Xu; Bao Zhang; Chiping Kong; Lei Fang; Xiaoping Gao; Leyi Sun; Lekang Li; Xiaoling Gong (Fishes, 2025)
The ten-year fishing ban on the Yangtze River aims to restore aquatic biodiversity and rebuild fishery resources. Megalobrama skolkovii, a key species in the basin, was investigated using 2024 data to provide a preliminary assessment of its population structure, stock dynamics, and early recovery. Age analysis (n = 243) showed that 1–6-year-olds were dominated by fish aged 3 (35%), with few older than 4, indicating moderate structural truncation. Growth parameters modeled by the von Bertalanffy Growth Function yielded L∞ = 61.89 cm and k = 0.25 year−1, with a weight–growth inflection age of 4.4 years. Natural mortality (M = 0.48 year−1) was estimated using Pauly’s empirical formula, and total mortality (Z = 0.55 year−1) was estimated from the catch curve analysis. While fishing mortality (F) was statistically indistinguishable from zero, a plausible low-intensity fishing scenario was explored to assess potential impacts of residual activities. Length-based indicators (LBIs) showed Pmat = 46.05%, Popt = 9.51%, and Pmega = 6.88%, suggesting reproductive recovery but incomplete structural restoration. These preliminary findings reveal an asymmetrical recovery trajectory, whereby physiological improvements and enhanced recruitment have occurred, yet full structural restoration remains incomplete. This underscores the need for continued, long-term conservation and monitoring to support population resilience.

Andrograpalides A–N, structurally diverse ent-labdane diterpenoids with anti-inflammatory activities from the leaves of Andrographis paniculata - Xiao Zhang; Yan-Zhen Li; Ya-Ting Lai; Wei Zeng; Min Yu; Jun-Tao Huang; Hong-Lei Jin; Wei-Qun Yang; Zhong-Xiang Zhao (Phytochemistry, 2025)

Ni nanoparticles inlaid in amorphous silicon nitride-derived nickel phyllosilicate: A highly stable and active catalyst for ammonia decomposition - Han Yang; Jing Li; Qiang Chang; Qun-chao Zhao; Meng-na Zhang; Huan-jiang Wang; Cheng-hua Zhang; Fei Wang; Xiao-dong Wen (Fuel, 2025)

Electrochemical degradation of toluene-2,4-diamine by graphene oxide-modified Ti/Sb-SnO2/α-PbO2/β-PbO2 anode: Performance and mechanism - Shuaishuai Man; Jun Zhang; Hebin Bao; Yifan Ge; Youcun Bai; Xinyu Liu; Ziyang Li; Liwei Qiu; Zhenzhen Zhao; Qun Yan (Environmental Research, 2025)

Molybdenum isotopes record slab inputs to the mantle source of late Triassic Arc Lavas, Northeast China - Zhigang Wang; Hui-Dong Zhang; Li-Qun Dai; Zi-Fu Zhao; Wei Fang (Chemical Geology, 2025)

Construction of new thermostable MtLPMO9V in synergism with cellulases for efficient lignocellulosic hydrolysis - Weimeng Li; Hang Yuan; Yun Hu; Shaohua Dou; Ezhen Zhang; Qun Wu; Fubao Sun (Bioresource Technology, 2025)

Research progress on electrochemiluminescence nanomaterials and their applications in biosensors - A review - Ming-Zhu Deng; Ming-Yu Zhong; Meng-Li Li; Gui-Qun Huang; Hao He; Xiao Xiao; Ruo-Bing Bai; Ruchika Hansanie Ukwatta; Li Mi; Ting-Ting Zhang; Yong-Hong Hu; Hui-Cheng Shi; et al. (Analytica Chimica Acta, 2025)

Suppression of TaHDA8-mediated lysine deacetylation of TaAREB3 acts as a drought-adaptive mechanism in wheat root development - Zehui Liu; Qun Yang; Xingbei Liu; Jinpeng Li; Lei Zhang; Wei Chu; Jingchen Lin; Debiao Liu; Danyang Zhao; Xiao Peng; Chaowu Zeng; Mingming Xin; et al. (Molecular Plant, 2025)

Analysis of rancidity characteristics of different foxtail millet flour during accelerated aging storage - Sufen Li; Zixi Wang; Jipeng Zhang; Xiaoshuang Zou; Qingyu Zhao; Qun Shen (Journal of Cereal Science, 2025)

Diffusion-driven zircon Zr isotopic fractionation during ultramafic–mafic magmatic differentiation - Li-Tao Ma; Li-Qun Dai; Shao-Bing Zhang; Ren-Xu Chen; Qiong-Xia Xia; Zi-Fu Zhao (Geochimica et Cosmochimica Acta, 2025)

Strengthening the d-p orbital hybridization of N-doped carbon nanocages with encapsulated Fe nanoparticles for efficient electromagnetic wave absorption - Pan Zhang; Qi Wei; Jiaqi Su; Xinyu Guo; Pei Kang Shen; Zian Li; Zhi Qun Tian (Chemical Engineering Journal, 2025)

The microbiome, metabolome, and correlation analysis reveal the beneficial role of the commensal Shewanella sp. MR-7 in foodborne enteritis in turbot (Scophthalmus maximus L.) - Chao-Qun Li; Wen-Yi Wang; Xin Wen; Si-Yu Qi; Jia-Ning Xu; Dan-Yu Wu; Kang-Di Tian; Chun-Yang Zhang; Bei-Li Zhang; Qin-Yuan Ma (Aquaculture, 2025)

Mineral types dominate microbiomes and biogeochemical cycling in acid mine drainage - Ye Huang; Xiu-Tong Li; Zhen Jiang; Zong-Ling Liang; Wan Liu; Zheng-Hua Liu; Liang-Zhi Li; Zhen-Ni Yang; Guo-Qing Zhang; Hua-Qun Yin; Jie-Liang Liang; Nan Zhou; et al. (Water Research, 2025)

Rapid detection of the viability of naturally aged maize seeds using multimodal data fusion and explainable deep learning techniques - He Li; Yilin Mao; Yanan Xu; Keling Tu; Han Zhang; Riliang Gu; Qun Sun (Food Chemistry, 2025)

New insights into cold plasma-induced starch modification: A comparative analysis of microstructure and physicochemical properties in A-type and B-type starches - Zhenyu Liu; Xilu Zhang; Zerui Li; Yunhao Lu; Zhenghong Xu; Qun Shen; Yuanlong Chi (Food Chemistry, 2025)

Short-Term Prediction of Ship Heave Motion Using a PSO-Optimized CNN-LSTM Model - Guowei Li; Gang Tang; Jingyu Zhang; Qun Sun; Xiangjun Liu (Journal of Marine Science and Engineering, 2025)
When ships conduct offshore operations in the ocean, they are subject to disturbances from natural factors such as sea breezes and waves. These disturbances lead to movements detrimental to the ship’s stability, especially heave movement in the vertical direction, which profoundly impacts the safety of shipboard facilities and staff. To counter this, the active wave compensation device is widely used on ships to maintain the stability of the working environment. However, the system’s efficiency and accuracy are compromised by the significant delay incurred while obtaining real-time motion signals and driving the actuator for motion compensation. To solve the time delay problem of shipborne wave compensation equipment in motion compensation under complex sea conditions, it is necessary to improve the ship heave motion prediction accuracy in an active wave compensation system. This paper presents a prediction method of ship heave motion based on the particle swarm optimization (PSO) and convolutional neural network–long short-term memory (CNN-LSTM) hybrid prediction model. The paper begins by establishing the ship heave motion model based on the P–M spectrum and slice theory, simulating the ship heave motion curve under different sea conditions on MATLAB. This simulation provides crucial data for the subsequent prediction model. The paper then delves into the realization method of ship heave motion based on PSO-CNN-LSTM, where the convolutional neural network (CNN) is used to extract the features of the input signal, thereby enhancing the multi-source feature fusion ability of the LSTM neural network model. The PSO algorithm is then employed to optimize the network structure and hyperparameters of the convolutional neural network. The experiments demonstrate that the proposed PSO-CNN-LSTM hybrid model effectively addresses the problem of predicting drift and boasts significantly higher prediction accuracy, making it suitable for predicting the short-term heave motion of ships. The data show that the optimized root mean square error (RMSE) value under level 5 sea conditions is 0.01265 compared to 0.01673 before optimization, and the optimized RMSE value under level 6 sea conditions is 0.01140 compared to 0.01479 before optimization, which demonstrates that the error between the predicted value and the actual value of the model decreases. This improved accuracy provides reassurance in the model’s predictive capabilities and lays the foundation for improving the accuracy of the motion compensation system in the future.

COP1 Overexpression Attenuates Nociceptive Behaviors and Neuroinflammation in Cancer-Induced Bone Pain by Suppressing c/EBPβ - Dan-Yang Li; Lin Liu; Shao-Jie Gao; Dai-Qiang Liu; Long-Qing Zhang; Jia-Yi Wu; Fan-He Song; Xin-Yi Dai; Ya-Qun Zhou; Wei Mei (Journal of Neuroimmune Pharmacology, 2025)

Assessing anthropogenic contributions and uncovering inter-regional periodic patterns of ground ozone with high-resolution predictions in 2015–2019 across China - Junshun Wang; Jin Dong; Runkui Li; Xiaoping Zhang; Qun Xu; Xianfeng Song (Science of The Total Environment, 2025)

Angle-resolved magneto-chiral anisotropy in a non-centrosymmetric atomic layer superlattice - Long Cheng; Mingrui Bao; Xue Zhang; Jingxian Zhang; Qun Yang; Qiang Li; Hui Cao; Dawei Qiu; Hui Li; Guanglei Cheng; Hua Zhou; Jian-Min Zuo; et al. (Science Bulletin, 2025)

Aggregation behavior of photoaging nanoplastics in artificial sweat solutions - Yanlin Yang; Haoran Song; Yan Cao; Jiao Li; Jie Li; Xiangfen Cui; Xuewei Hu; Anjum Mahfuza; Ping Ning; Linfeng Zhang; Qun Zhao; Senlin Tian (Journal of Hazardous Materials, 2025)

Differences in starch and protein composition, morphological and structure, and their impacts on eating quality of soft japonica rice under different light and nitrogen fertilizer conditions in southern China - Zhongtao Ma; Jianghui Yu; Xi Chen; Jiale Cao; Ying Zhu; Guodong Liu; Guangyan Li; Fangfu Xu; Qun Hu; Hongcheng Zhang; Haiyan Wei (Food Chemistry, 2025)

Association of greenness exposure with serum vitamin D status and effects of ambient particulate matter among pregnant women in early pregnancy - Dongjian Yang; Yanling Shen; Qun Wang; Xin Sun; Mengxiang Li; Jinjing Shi; Lei Chen; Jun Zhang; Xinhua Ji (Environmental Pollution, 2025)

The application of marine bioactive composite materials in environmental remediation - Yanan Huang; Hao Li; Ronglian Xing; Xiaorui Chen; Yuxin Sun; Meichen Tian; Ran Zhang; Xin Wang; Xinxin Wang; Rui Li; Lihong Chen; Hongxia Zhang; et al. (Desalination, 2025)

Nitrogen addition and plant functional type mediate the mesofauna-driven litter element release of subtropical forest - Jihong Li; Qun Liu; Rui Yin; Chengming You; Li Zhang; Han Li; Lixia Wang; Hongwei Xu; Lin Xu; Sining Liu; Bo Tan; Zhenfeng Xu (Plant and Soil, 2025)

A genomic variation map provides insights into potato evolution and key agronomic traits - Qun Lian; Yingying Zhang; Jinzhe Zhang; Zhen Peng; Weilun Wang; Miru Du; Hongbo Li; Xinyan Zhang; Lin Cheng; Ran Du; Zijian Zhou; Zhenqiang Yang; et al. (Molecular Plant, 2025)

Comprehensive assessment, intelligent prediction, and precise mitigation strategies for greenhouse gas emissions in full-scale wastewater treatment plants - Zitan Zhang; Fei Qi; Yao Liu; Muhammad Bilal Asif; Amir Ikhlaq; Zhenbei Wang; Caocao Chen; Chen Li; Jing Chang; Qun Li; Ye Li; Yujie Li; et al. (Environmental Research, 2025)

The Drainage Dysfunction of Meningeal Lymphatic Vessels Is Correlated with the Recurrence of Chronic Subdural Hematoma: a Prospective Study - Jiahao Zhang; Lei Yu; Xiaoyu Wang; Qian Yu; Bingrui Zhu; Haocheng Zhang; Yibo Liu; Huaming Li; Anke Zhang; Kaikai Wang; Yezhao He; Qun Wu; et al. (Translational Stroke Research, 2025)

Rapid detection of corn seed turtle cracks based on transmitted light image and deep learning method - He Li; Yun Hao; Weifeng Wu; Keling Tu; Yanan Xu; Han Zhang; Danyang Zhang; Mingliu Li; Riliang Gu; Qun Sun (Computers and Electronics in Agriculture, 2025)

Multi-scale spatiotemporal patterns of urban climate effects and their driving factors across China - Panli Cai; Runkui Li; Jingxian Guo; Zhen Xiao; Haiyu Fu; Tongze Guo; Tianyi Wang; Xiaoping Zhang; Qun Xu; Xianfeng Song (Urban Climate, 2025)

BarH1 regulates the expression of conserved odorant-binding protein 22 from Dastarcus helophoroides - Rui-Nan Yang; Dong-Zhen Li; Ao Liu; Yi Wei; Rui-Lin Zhang; Hazem Abdelnabby; Man-Qun Wang (Insect Biochemistry and Molecular Biology, 2025)

Synthesis of phosphorylated covalent organic frameworks with different linkages–Critical factors controlling the extraction of uranium from highly acidic media - Xiao-Yi Tang; Hui-Di Zhang; Zi-Jie Li; Shuai Wang; Si-Yan Liu; Tao-Yuan Xiu; Ji-Pan Yu; Lin Wang; Li-Yong Yuan; Wang-Suo Wu; Wei-Qun Shi (Chemical Engineering Journal, 2025)

Temporal dynamics of bacterial biofilms and their relationship with heavy metals on expanded polystyrene microplastics - Qun Xie; Yan Feng; Xiangrong Xu; Hengxiang Li; Lang Lin; Weiqiong Yu; Guanghui Zhu; Nenghao Zhong; Minhua Wu; Kai Zhang (Journal of Oceanology and Limnology, 2025)

Nutrient addition alters drought resistance and resilience via forb abundance in a temperate grassland - Dengnan Luo; Guojiao Yang; Guangru Zhang; Qianguang Liu; Qun Guo; Shenggong Li; Yun Xie; Zhongmin Hu (Agriculture, Ecosystems & Environment, 2025)

Characterizing multi-source heavy metal contaminated sites at the Hun River basin: An integrated deep learning and data assimilation approach - Yanhao Wu; Mei Li; Haijian Xie; Yanghui Shi; Qun Li; Shaopo Deng; Shengtian Zhang (Journal of Hydrology, 2025)

Machine learning discovery of novel antihypertensive peptides from highland barley protein inhibiting angiotensin I-converting enzyme (ACE) - Xin Bao; Yiyun Zhang; Liyang Wang; Zijian Dai; Yiqing Zhu; Mengyao Huo; Rong Li; Yichen Hu; Qun Shen; Yong Xue (Food Research International, 2025)

Improving the prebiotic activity and oxidative stability of carboxymethyl curdlan − quercetin conjugates stabilized Pickering emulsions for the colonic targeting delivery of curcumin - Huan Li; Wenjiang He; Zijun Wang; Qun Zhang; Die Hu; Ke Ding; Qiutao Xie; Yanqun Xu; Yang Shan; Shenghua Ding (Food Research International, 2025)

Salinity affects C/N ratio through differential responses of carbon and nitrogen metabolism in mangrove Avicennia marina leaves revealed by combined analysis of transcriptome and metabolome - Jing Li; Ling-Yu Song; Ze-Jun Guo; Chao-Qun Xu; Lu-Dan Zhang; Ji-Cheng Wang; Han-Chen Tang; Ming-Jin Dai; Xue-Yi Zhu; Hai-Lei Zheng (Plant and Soil, 2025)

A pilot study on oral microbiome in electronic cigarettes consumers versus traditional cigarettes smokers - Jilong Liu; Qiulin Yue; Song Zhang; Jing Xu; Xingtao Jiang; Qun Su; Lei Sun; Baojun Li; Kunlun Li; Le Su; Lin Zhao (Folia Microbiologica, 2025)

Ecological Differentiation Among Nitrous Oxide Reducers Enhances Temperature Effects on Riverine N 2 O Emissions - Sibo Zhang; Meijuan Yang; Xinghui Xia; Qinyuan Gu; Qun Gao; Junfeng Wang; Shaoda Liu; Xiaokang Li; Yingjie Li; William H. McDowell; Zhifeng Yang (Global Change Biology, 2025)
Nitrous oxide (N 2 O) reductase, the sole natural microbial sink for N 2 O, exists in two microbial clades: nosZ I and nosZ II. Although previous studies have explored inter‐clade ecological differentiation, the intra‐clade variations and their implications for N 2 O dynamics remain understudied. This study investigated both inter‐ and intra‐clade ecological differentiation among N 2 O reducers, the drivers influencing these patterns, and their effects on N 2 O emissions across continental‐scale river systems. The results showed that both nosZ I and nosZ II community turnovers were associated with similar key environmental factors, particularly total phosphorus (TP), but these variables explained a larger proportion of variation in the nosZ I community. The influence of mean annual temperature (MAT) on community composition increased for more widespread N 2 O‐reducing taxa. We identified distinct ecological clusters within each clade of N 2 O reducers and observed identical ecological clustering patterns across both clades. These clusters were primarily characterized by distinct MAT regimes, coarse sediment texture as well as low TP levels, and high abundance of N 2 O producers, with MAT‐related clusters constituting predominant proportions. Intra‐clade ecological differentiation was a crucial predictor of N 2 O flux and reduction efficiency. Although different ecological clusters showed varying or even contrasting associations with N 2 O dynamics, the shared ecological clusters across clades exhibited similar trends. Low‐MAT clusters in both the nosZ I and nosZ II communities were negatively correlated with denitrification‐normalized N 2 O flux and the N 2 O:(N 2 O + N 2 ) ratio, whereas high‐MAT clusters showed positive correlations. This contrasting pattern likely stems from low‐MAT clusters being better adapted to eutrophic conditions and their more frequent co‐occurrence with N 2 O‐producing genes. These findings advance our understanding of the distribution and ecological functions of N 2 O reducers in natural ecosystems, suggesting that warming rivers may have decreased N 2 O reduction efficiency and thereby amplify temperature‐driven emissions.

Soil legacies of genotypic diversity enhance population resistance to water stress - Zekang Liu; Cai Cheng; Qun Zhang; Xing Tian; Lin Jiang; Kerri M. Crawford; Xiang Liu; Jianquan Liu; Qiang He; Bo Li; Jihua Wu (Ecology, 2025)
While the positive relationship between plant diversity and ecosystem functioning is frequently observed and often attributed to direct plant–plant interactions, it remains unclear whether and how the effects of plant diversity endure through soil legacy effects, particularly at the level of genotypic diversity. We manipulated the genotypic diversity of Scirpus mariqueter and tested its soil legacy effects on a conspecific phytometer under low‐ and high‐water availability conditions. We found that genotypic diversity enhanced phytometer productivity through soil legacies, with stronger effects under low‐water availability conditions, improving its resistance to water stress. Moreover, this effect was attributed to the association between asexual and sexual reproductive strategies by increasing ramet number to ensure plant survival under low‐water availability and promoting sexual reproduction to escape stress. The observed diversity effects were primarily associated with increased levels of microbial biomass in soils trained by populations with diverse genotypes. Our findings highlight the importance of plant genotypic diversity in modulating ecosystem functioning through soil legacies and call for management measures that promote genetic diversity to make ecosystems sustainable in the face of climate change.

Bipolaristeroid A, a 5,6-seco-9,10-seco-steroid with cytotoxic activity from the fungus Bipolaris maydis - Yong Shen; Lianghu Gu; Qun Zhou; Xiaotian Zhang; Mengru Yu; Qin Li; Yu Liang; Chunmei Chen; Yonghui Zhang; Hucheng Zhu (Phytochemistry, 2025)

Simultaneously enhancing efficiency and thermo-/UV-stability of organic solar cells by regulating the nanomorphology of the polymer blend by an acrylated fullerene derivative - Haitao Song; Yaqian Dong; Zesheng Zhang; Jin Fang; Chao Yue; Yongzhen Yang; Chao Liu; Qing Guo; Hua Wang; Qun Luo; Wei-Shi Li; Lingpeng Yan; et al. (Chemical Engineering Journal, 2025)

Palynological evidence for the Late Cretaceous lake transgression event in the Songliao Basin, NE China - Qun Yang; Qiaoer Ying; Liqin Li; Jian Zhang; Fanhao Gong; Shouliang Sun; Hongshan Wang; Xiao Tan; Fei Liang (Cretaceous Research, 2025)

Pyridoxine supplementation before puberty ameliorates MAM-induced cognitive and sensorimotor gating impairments - Cheng Xue; Xiao-Hui Li; Hong-Qun Ding; Xin Qian; Meng-Yu Zhang; Kai Chen; Zi-Wei Wei; Ying Li; Jun-Hai Jia; Wei-Ning Zhang (Metabolic Brain Disease, 2024)

Mechanism of antimony oxidation and adsorption using immobilized Klebsiella aerogenes HC10 in soil - Qun Rong; Dingtian Lu; Kai Zhong; Shu Yang; Zhongyi Li; Chaolan Zhang (Science of The Total Environment, 2024)

Polystyrene microplastics alleviate the developmental toxicity of silver nanoparticles in embryo-larval zebrafish (Danio rerio) at the transcriptomic level - Qiao-hong Xiao; Hao Xiang; Ya-nan Tian; Jiao-long Huang; Ming-qun Li; Pu-qing Wang; Kai Lian; Peng-xia Yu; Meng-yao Xu; Ruo-nan Zhang; Yan Zhang; Jie Huang; et al. (Science of The Total Environment, 2024)

Calcium regulates the physiological and molecular responses of Morus alba roots to cadmium stress - Ming-Jin Dai; Lu-Dan Zhang; Jing Li; Chun-Quan Zhu; Ling-Yu Song; He-Zi Huang; Chao-Qun Xu; Qing-Hua Li; Lin Chen; Chen-Kai Jiang; Hong-Ling Lu; Qiu-Tong Ling; et al. (Journal of Hazardous Materials, 2024)

AmTPS6 promotes trehalose biosynthesis to enhance the Cd tolerance in mangrove Avicennia marina - Ling-Yu Song; Jing Li; Lu-Dan Zhang; Zhao-Yu Guo; Chao-Qun Xu; Li-Wei Jiang; Jin-Yu Liu; Ji-Cheng Wang; Qing-Hua Li; Han-Chen Tang; Hai-Lei Zheng (Journal of Hazardous Materials, 2024)

Interaction of diesel exhaust particulate matter with mucins in simulated saliva fluids: Bioaccessibility of heavy metals and potential health risks - Jiao Li; Haorang Song; Linfeng Zhang; Jie Li; Yanlin Yang; Xiangfen Cui; Anjum Mahfuza; Yan Cao; Xuewei Hu; Chen Li; Qun Zhao; Senlin Tian (Journal of Hazardous Materials, 2024)

Synthesis of magnetically recyclable FeCeO nanocrystals with heterojunction between Fe2O3 and CeO2 via one-step method toward efficient organic dyes degradation by activating peroxymonosulfate - Liang Li; Chao-qun Wu; De-xiang Sun; Nan Zhang; Ting Huang; Yong Wang (Journal of Cleaner Production, 2024)

Identification of a vital transcription factor of the alanine aminotransferase in the brown planthopper and its upstream regulatory pathways - Li-Qun Wang; Shi-Hui Li; Wen-Qing Zhang (Insect Biochemistry and Molecular Biology, 2024)

Environmental exposure to cadmium induces olfactory neurotoxicity in fire ants and the molecular basis - Xiaohui Xiao; Wenzhen Zhao; Yikang Shao; Changyuan Hu; Jinlong Liu; Guoqing Zhang; Fuxiang Yang; Jing Zhao; Yueguan Fu; Lei Li; Man-Qun Wang; Aiming Zhou (Environmental Pollution, 2024)

Ultrahigh-performance and broadband photodetector from visible to shortwave infrared band based on GaAsSb nanowires - Yubin Kang; Xiaobing Hou; Zhihong Zhang; Jilong Tang; Fengyuan Lin; Kexue Li; Qun Hao; Zhipeng Wei (Chemical Engineering Journal, 2024)

Jeotgalibacillus haloalkalitolerans sp. nov., a novel alkalitolerant and halotolerant bacterium, isolated from the confluence of the Fenhe River and the Yellow River - Ya-Fei Zhang; Yun-Lin Peng; Yong-Hui Xiao; Bing Yu; Ming-Yue Cao; Zhi-Ling Zhang; Le-Qun Huang; Yi Li (Antonie van Leeuwenhoek, 2024)

Facilitating Response/Recovery of cellulosic humidity sensor by Densificating fibril Arrays - Mengru Geng; Jiaqi Zhao; Jie Li; Boyue Liu; Ruiming Liu; Xiaojuan Wang; Wanlong Song; Mingzhe Shao; Yihao Luan; Qun Li; Meng Gao; Fengshan Zhang; et al. (Chemical Engineering Journal, 2024)

A 3D aerogel evaporator for efficient solar interfacial evaporation: Breaking through the upper limit of steam production rate - Zhaoshun Zhang; Qi Zhang; Hui Zhang; Xueqin Zuo; Qun Yang; Huaibao Tang; Shaowei Jin; Guang Li (Chemical Engineering Journal, 2024)

Fabrication of graphene oxide/ammonium molybdophosphate composite membrane for decontamination of cesium ions from seawater - Xiao-Yi Tang; Zi-Jie Li; Lin Wang; Peng-Cheng Zhang; Kong-Qiu Hu; Li-Rong Zheng; Zhi-Hui Zhang; Li-Yong Yuan; Wang-Suo Wu; Wei-Qun Shi (Chemical Engineering Journal, 2024)

Concentration and activation biresponsive strategy in one analysis system with simultaneous use of G4 structure-specific signal probe and enzyme-catalyzed reaction - Yu-Shu Li; Chun-Feng Feng; Hao-Ran Chen; Wei-Guo Yang; Fei Liu; Ming-Li Su; Ruo Yuan; Li-Qun Zhang; Wen-Bin Liang (Analytica Chimica Acta, 2024)

Seasonal soil water dynamics under different tree plants and mulching treatments in the Loess Hilly Region of China - Xing Wang; Kemeng Zhang; Jing Li; Qun Li; Wenjuan Na; Yuankang Gao; Zhiyong Gao (Ecological Engineering, 2024)

Enhanced solar-driven steam generation and water purification using 3D arch solar evaporators - Yong-Gang Wu; Chao-Hua Xue; Xiao-Jing Guo; Meng-Chen Huang; Hui-Di Wang; Chao-Qun Ma; Li Wan; Shi-Qiang Lv; Wen-Min Zhang; Rong-Rong Gao (Desalination, 2024)

Programmable bionanocomposite coated fertilizers for prolonged controlled release of nitrogen - Jiaxuan Liu; Yue Yuan; Ji Gao; Zhaoxian Qin; Wenbo Peng; Akanksha Lakra; Yuxuan Zhang; Shugang Zhang; Guodong Liu; Yongsheng Chen; Qun Li; Zhaohui Tong (Chemical Engineering Journal, 2024)

Chloride homeostasis via enhanced salt ion secretion selectivity contributes to salt tolerance of recretohalophytic mangrove Avicennia marina - Qian-Su Ding; Chao-Qun Xu; Dong-Na Ma; Ming-Yue Wei; Chang-Hao Gao; Shan Zhang; Huan Li; Xue-Yi Zhu; Hai-Lei Zheng (Plant and Soil, 2024)

Matrine inhibits invasion and migration of gallbladder cancer via regulating the PI3K/AKT signaling pathway - Rong-Liang Mo; Zhuang Li; Peng Zhang; Ming-Hui Sheng; Gen-Cheng Han; Deng-Qun Sun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Liquidambaric acid inhibits the proliferation of hepatocellular carcinoma cells by targeting PPARα-RXRα to down-regulate fatty acid metabolism - Xinyun Zhao; Xinping Zhu; Honglei Tao; Hongling Zou; Jili Cao; Yuxin Chen; Ziru Zhang; Yongqiang Zhu; Qun Li; Mingqian Li (Toxicology and Applied Pharmacology, 2024)

Simultaneous efficient evaporation and stable electricity generation enabled by a wooden evaporator based on composite photothermal effect - Wang Lu; Dexing Jiang; Zhaofeng Wang; Xu Zhang; Qun Ding; Zhuo Zhang; Xiaowei Liu; Long Bai; Zhiguo Li; Yang Liu (Chemical Engineering Journal, 2024)

Scalable thermochromic superhydrophobic collagen fiber-based wearable materials for all-weather self-adaptive radiative cooling and solar heating - Meng-Chen Huang; Chao-Hua Xue; Zhongxue Bai; Hui-Di Wang; Chao-Qun Ma; Yong-Gang Wu; Li Wan; Long Xie; Shi-Qiang Lv; Rong-Rong Gao; Wen-Min Zhang; Jun Cheng; et al. (Chemical Engineering Journal, 2024)

Molybdenum isotopic evidence for the initiation of a big mantle wedge beneath eastern Asia - Wei Fang; Li-Qun Dai; Zi-Fu Zhao; Qi Chen; Jun Yan; Dayu Zhang; Ding-Sheng Jiang (Chemical Geology, 2024)

More sensitive microbial responses to the interactive effects of warming and altered precipitation in subsoil than topsoil of an alpine grassland ecosystem - Qi Qi; Shijie Ning; Xue Guo; Jianshu Zhao; Renmao Tian; Haoran Gui; Jin‐Sheng He; Hao Wang; Zhenhua Zhang; Konstantinos T. Konstantinidis; Qun Gao; Yuxin Wang; et al. (Global Change Biology, 2024)
Subsoil is a large organic carbon reservoir, storing more than half of the total soil organic carbon (SOC) globally. Conventionally, subsoil is assumed to not be susceptible to climate change, but recent studies document that climate change could significantly alter subsoil carbon cycling. However, little is known about subsoil microbial responses to the interactive effects of climate warming and altered precipitation. Here, we investigated carbon cycling and associated microbial responses in both subsoil (30–40 cm) and topsoil (0–10 cm) in a Tibetan alpine grassland over 4 years of warming and altered precipitation. Compared to the unchanged topsoil carbon ( β = .55, p = .587), subsoil carbon exhibited a stronger response to the interactive effect of warming and altered precipitation ( β = 2.04, p = .021), that is, warming decreased subsoil carbon content by 28.20% under decreased precipitation while warming increased subsoil carbon content by 18.02% under increased precipitation.Furthermore, 512 metagenome‐assembled genomes (MAGs) were recovered, including representatives of phyla with poor genomic representation. Compared to only one changed topsoil MAG, 16 subsoil MAGs were significantly affected by altered precipitation, and 5 subsoil MAGs were significantly affected by the interactive effect of warming and precipitation. More than twice as many populations whose MAG abundances correlated significantly with the variations of carbon content, components and fluxes were observed in the subsoil than topsoil, suggesting their potential contribution in mediating subsoil carbon cycling. Collectively, our findings highlight the more sensitive responses of specific microbial lineages to the interactive effects of warming and altered precipitation in the subsoil than topsoil, and provide key information for predicting subsoil carbon cycling under future climate change scenarios.

Exposure to O3 and NO2 on the interfacial chemistry of the pulmonary surfactant and the mechanism of lung oxidative damage - Jie Li; Haoran Song; Tao Luo; Yan Cao; Linfeng Zhang; Qun Zhao; Zhanchao Li; Xuewei Hu; Junjie Gu; Senlin Tian (Chemosphere, 2024)

The microbial electrolysis cell combined with anaerobic digestion for high salinity landfill leachate treatment: Operation parameter optimization, microbial analysis and degradation pathways - Jiachen Zhu; Qun Zhang; Mengmeng Li; Faqian Sun; He Liu; Minhua Cui; Chongjun Chen (Journal of Water Process Engineering, 2024)

Triphenylamine promoted geometric structure adjusting of the novel macrocyclic structure D-π-A conjugated microporous polymers for photocatalytic hydrogen evolution - Fengrui Li; Xiao Dai; Linfeng Zhang; Huadong Wu; Jianding Li; Jia Guo; Qun Yi (Fuel, 2024)

Utilization of the waste aqueous phase from tea residue hydrothermal carbonization for preparing active food packaging films - Wenhui Zheng; Danmin Yang; Xu Zeng; Qun Liu; Chunchun Wang; Xialing Wu; Meng Li; Yue Liu; Linjing Chen; Wuyin Weng; Yucang Zhang (Food Chemistry, 2024)

Improving ion rejection by optimizing the structure and charge distribution of the Janus membrane - Zhe Zhang; Zhenquan Li; Yanxin Shi; Nan Qiao; Jiaqiang Liao; Zhi Qun Tian; Changzheng Li (Desalination, 2024)

Esketamine Prevents Postoperative Emotional and Cognitive Dysfunction by Suppressing Microglial M1 Polarization and Regulating the BDNF-TrkB Pathway in Ageing Rats with Preoperative Sleep Disturbance - Yuxin Wen; Jiawen Xu; Jiahong Shen; Zili Tang; Shuxin Li; Qun Zhang; Jiaqi Li; Jianliang Sun (Molecular Neurobiology, 2024)
Postoperative depression (POD) and postoperative cognitive dysfunction (POCD) have placed heavy burden on patients’ physical and mental health in recent years. Sleep disturbance before surgery is a common phenomenon that has been increasingly believed to affect patients’ recovery, especially in aged patients, while little attention has been paid to sleep disruption before surgery and the potential mechanism remains ambiguous. Ketamine has been reported to attenuate POCD after cardiac surgery and elicit rapid-acting and sustained antidepressant actions. The present study aimed to clarify the effect of esketamine’s (the S-enantiomer of ketamine) protective effects and possible mechanisms of action in POCD and POD. Our results showed that sleep disturbance before surgery exacerbated microglial M1 polarization and microglial BDNF-TrkB signalling dysfunction induced by surgery, resulting in postoperative emotional changes and cognitive impairments. Notably, treatment with esketamine reversed the behavioural abnormalities through inhibiting the M1 polarization of microglia and the inflammatory response thus improving BDNF-TrkB signalling in vivo and vitro. In addition, esketamine administration also reversed the impaired hippocampal synaptic plasticity which has been perturbed by sleep disturbance and surgery. These findings warrant further investigations into the interplay of esketamine and may provide novel ideas for the implication of preoperative preparations and the prevention of postoperative brain-related complications.

Dual N-linked glycosylation at residues 133 and 158 in the hemagglutinin are essential for the efficacy of H7N9 avian influenza virus like particle vaccine in chickens and mice - Yufei Wang; Qun Li; Peipei Peng; Qi Zhang; Yalan Huang; Jiao Hu; Zenglei Hu; Xiufan Liu (Veterinary Microbiology, 2024)

The first detection of mpox virus DNA from wastewater in China - Jin Xu; Chao Liu; Qun Zhang; Haining Zhu; Feng Cui; Zhiqiang Zhao; Mingfang Song; Bo Zhou; Yunxiao Zhang; Peilong Hu; Lei Li; Qin Wang; et al. (Science of The Total Environment, 2024)

In situ mass spectrometry imaging reveals pesticide residues and key metabolic pathways throughout the entire cowpea growth process - Shufan Jiang; Jingling Lin; Rui Zhang; Qiong Wu; Hongxing Li; Qun Zhang; Mingyue Wang; Longjun Dai; Defang Xie; Yue Zhang; Xinzhong Zhang; Bingjun Han (Journal of Hazardous Materials, 2024)

Pilot-scale field studies on activated microbial remediation of petroleum-contaminated soil - Wu-Juan Sun; Qian Li; Bo-Yun Luo; Rui Sun; Cong-Yu Ke; Si-Chang Wang; Qun-Zheng Zhang; Xun-Li Zhang (Environmental Geochemistry and Health, 2024)

Identification of candidate genes for Fusarium head blight resistance from QTLs using RIL population in wheat - Mingxia Zhang; Peng Jiang; Qun Wu; Xu Han; Junxia Man; Junsheng Sun; Jinlong Liang; Jingchuan Chen; Qi Zhao; Ying Guo; Yanrong An; Haiyan Jia; et al. (Plant Molecular Biology, 2024)

Draft Genome Sequence of Candida saopaulonensis from a Very Premature Infant with Sepsis - Ya-Ting Ning; Rong-Chen Dai; Zheng-Yu Luo; Meng Xiao; Yingchun Xu; Qun Yan; Li Zhang (Mycopathologia, 2024)
The rare fungus Candida saopaulonensis has never been reported to be associated with human infection. We report the draft genome sequence of the first clinical isolate of C. saopaulonensis, which was isolated from a very premature infant with sepsis. This is the first genome assembly reaching the near-complete chromosomal level with structural annotation for this species, opening up avenues for exploring evolutionary patterns and genetic mechanisms of pathogenesis.

Improved bacterial composition and co-occurrence patterns of rhizosphere increased nutrient uptake and grain yield through cultivars mixtures in maize - Xucun Jia; Haipeng Shang; Yibo Chen; Mengjie Lin; Yuepeng Wei; Yuxia Li; Rongfa Li; Pengfei Dong; Yinglong Chen; Yongen Zhang; Qun Wang (Science of The Total Environment, 2024)

Sublethal effect and detoxifying metabolism of metaflumizone and indoxacarb on the fall armyworm, Spodoptera frugiperda - Li Zhang; Hui-Zi Wu; Pei-Yun He; Hai-Qun Cao; Wan-Na Zhang; Ying-Chuan Peng; Cheng-Wang Sheng (Pesticide Biochemistry and Physiology, 2024)

Coupling effect of vacancy defects and multi-adsorption sites in porous carbon cathode for high-performance aqueous zinc-ion hybrid capacitors - Heng-Xiang Li; Wen-Jing Shi; Ling-Yang Liu; Xiaohua Zhang; Peng-Fang Zhang; Qun Wang; Ying Liu; Zhao-Yang Wang; Jianmin Dou (Chemical Engineering Journal, 2024)

Chinese Society of Cardiology guidelines on the diagnosis and treatment of adult fulminant myocarditis - Jiangang Jiang; Hongyang Shu; Dao Wen Wang; Rutai Hui; Chenze Li; Xiao Ran; Hong Wang; Jing Zhang; Shaoping Nie; Guanglin Cui; Dingcheng Xiang; Qun Shao; et al. (Science China Life Sciences, 2024)

GWAS determined genetic loci associated with callus induction in oil palm tissue culture - Yin Min Htwe; Peng Shi; Dapeng Zhang; Zhiying Li; Qun Yu; Yong Wang (Plant Cell Reports, 2024)

Emergence of a clinical Salmonella enterica serovar 1,4,[5], 12: i:-isolate, ST3606, in China with susceptibility decrease to ceftazidime-avibactam carrying a novel blaCTX-M-261 variant and a blaNDM-5 - Jie Wei; Shimei Shen; Qinghuan Zhang; Jinping Lu; Shenglan Mao; Chunhong Zou; Hua Zhou; YeLin Wei; Xingyi Ou; Jinyu Huang; Deqiang Wang; Xiaobin Li; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose The detection rate of Salmonella enterica serovar 1,4,[5], 12: i: - (S. 1,4,[5], 12: i: -) has increased as the most common serotype globally. A S . 1,4,[5], 12: i: - strain named ST3606 (sequence type 34), isolated from a fecal specimen of a child with acute diarrhea hospitalized in a tertiary hospital in China, was firstly reported to be resistant to carbapenem and ceftazidime-avibactam. The aim of this study was to characterize the whole-genome sequence of S. 1,4,[5], 12: i: - isolate, ST3606, and explore its antibiotic resistance genes and their genetic environments. Methods The genomic DNA of S. 1,4,[5], 12: i: - ST3606 was extracted and performed with single-molecule real-time sequencing. Resistance genes, plasmid replicon type, mobile elements, and multilocus sequence types (STs) of ST3606 were identified by ResFinder 3.2, PlasmidFinder, OriTfinder database, ISfinder database, and MLST 2.0, respectively. The conjugation experiment was utilized to evaluate the conjugation frequency of pST3606-2. Protein expression and enzyme kinetics experiments of CTX-M were performed to analyze hydrolytic activity of a novel CTX-M-261 enzyme toward several antibiotics. Results Single-molecule real-time sequencing revealed the coexistence of a 109-kb IncI1-Iα plasmid pST3606-1 and a 70.5-kb IncFII plasmid pST3606-2. The isolate carried resistance genes, including bla NDM-5 , sul1 , qacE , aadA2 , and dfrA12 in pST3606-1, bla TEM-1B , aac (3)- lld , and bla CTX-M-261 , a novel bla CTX-M-1 family member, in pST3606-2, and aac (6')- Iaa in chromosome. The bla CTX-M-261 was derived from bla CTX-M-55 by a single-nucleotide mutation 751G>A leading to amino acid substitution of Val for Met at position 251 (Val251Met), which conferred CTX-M increasing resistance to ceftazidime verified by antibiotics susceptibility testing of transconjugants carrying pST3606-2 and steady-state kinetic parameters of CTX-M-261. pST3606-1 is an IncI1-α incompatibility type that shares homology with plasmids of pC-F-164_A-OXA140, pE-T654-NDM-5, p_dm760b_NDM-5, and p_dmcr749c_NDM-5. The conjugation experiment demonstrated that pST3606-2 was successfully transferred to the Escherichia coli recipient C600 with four modules of OriTfinder. Conclusion Plasmid-mediated horizontal transfer plays an important role in bla NDM-5 and bla CTX-M-261 dissemination, which increases the threat to public health due to the resistance to most β-lactam antibiotics. This is the first report of bla CTX-M-261 and bla NDM-5 in S. 1,4,[5], 12: i: -. The work provides insights into the enzymatic function and demonstrates the ongoing evolution of CTX-M enzymes and confirms urgency to control resistance of S . 1,4,[5], 12: i: -.

Monoterpenoid indole alkaloids from Alstonia scholaris and their Toxoplasma gondii inhibitory activity - Pei-Qian Wu; Zhen-Di Liu; Yu-Hao Ren; Jun-Su Zhou; Qun-Fang Liu; Yan Wu; Ji-Li Zhang; Bin Zhou; Jian-Min Yue (Phytochemistry, 2024)

Determining priority control toxic metal for different protection targets based on source-oriented ecological and human health risk assessment around gold smelting area - Yan Zhou; Da Ding; Yuanchao Zhao; Qun Li; Dengdeng Jiang; Zhengyong Lv; Jing Wei; Shengtian Zhang; Shaopo Deng (Journal of Hazardous Materials, 2024)

Tailoring biochar supported iron nanoparticles to activate persulfate for atrazine degradation in soil - Ruizhen Li; Xiaoqing Shen; Jiaxing Zhang; Qun Jiang; Lei Wang; Ying Zhang (Journal of Environmental Chemical Engineering, 2024)

Non-fitting functional representation for the equilibrium constant subject to reaction between H2S and CO2 - Chao-Wen Wang; Ji Li; Lie-Hui Zhang; Qun-Chao Ding; Guan-Hong Liu; Gao Li; Rui Jiang; Xiao-Long Peng; Lin-Sheng Wei; Hong-Ming Tang; Jian-Yi Liu; Chun-Sheng Jia (Fuel, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Membrane Trafficking-Related Genes Predict Tumor Immune Microenvironment and Prognosis in Colorectal Cancer - Zhou Ding; Lu Han; Qun Zhang; Jing Hu; Li Li; Xiaoping Qian (Biochemical Genetics, 2024)

Retraction Notice to “Pumped hydro energy storage arbitrage in the day-ahead market in smart grid using stochastic p-robust optimization method” [Sustainable Cities and Society 75 (2021) 103274] - Zhifeng Li; Qing Zhang; Qun Guo; Sayyad Nojavan (Sustainable Cities and Society, 2024)

Degradation of reburied archaeological wood piles after preservative treatment for twenty years - Yuanyuan Zong; Wenbo Zhang; Houjian Zhang; Dongqing Li; Qun Wang (International Biodeterioration & Biodegradation, 2024)

Propyl gallate exposure affects the mouse 2-cell stage embryonic development through inducing oxidative stress and autophagy - Sheng-Ji Yang; Fu-Yi Yang; Yi-Nuo Zou; Yong-Sheng Wang; Zhi-Ming Ding; Li-Dan Zhang; Xu Zhou; Ming Liu; Ze-Qun Duan; Li-Jun Huo (Food and Chemical Toxicology, 2024)

Interactions between inhalable aged microplastics and lung surfactant: Potential pulmonary health risks - Yan Cao; Qun Zhao; Fanshu Jiang; Yingxue Geng; Haoran Song; Linfeng Zhang; Chen Li; Jie Li; Yingjie Li; Xuewei Hu; Jianhong Huang; Senlin Tian (Environmental Research, 2024)

Genotype diversity enhances invasion resistance of native plants via soil biotic feedbacks - Cai Cheng; Zekang Liu; Qun Zhang; Xing Tian; Ruiting Ju; Bo Li; Mark van Kleunen; Jonathan M. Chase; Jihua Wu (Ecology Letters, 2024)
Although native species diversity is frequently reported to enhance invasion resistance, within‐species diversity of native plants can also moderate invasions. While the positive diversity–invasion resistance relationship is often attributed to competition, indirect effects mediated through plant–soil feedbacks can also influence the relationship. We manipulated the genotypic diversity of an endemic species, Scirpus mariqueter , and evaluated the effects of abiotic versus biotic feedbacks on the performance of a global invader, Spartina alterniflora . We found that invader performance on live soils decreased non‐additively with genotypic diversity of the native plant that trained the soils, but this reversed when soils were sterilized to eliminate feedbacks through soil biota. The influence of soil biota on the feedback was primarily associated with increased levels of microbial biomass and fungal diversity in soils trained by multiple‐genotype populations. Our findings highlight the importance of plant–soil feedbacks mediating the positive relationship between genotypic diversity and invasion resistance.

Heterostructure nanozymes with sustainable tumor microenvironment regulation and reinforced hyperthermia-responsive catalytic activities for orchestrated osteosarcoma catalytic therapy - Xing Zhang; Xiang Li; Mengying Fu; Jeremiah Ong'achwa Machuki; Wandong Wang; Liang Wu; Qun Zhao; Ning Xin; Lei Hua; Fenglei Gao (Chemical Engineering Journal, 2024)

Myricetin-based fluorescence probes with AIE and ESIPT properties for detection of hydrazine in the environment and fingerprinting - Wei Xiao; Qing Zhang; Dong Hui You; Wei Xue; Feng Peng; Nian Bing Li; Guang Ming Zhou; Hong Qun Luo (Analytica Chimica Acta, 2024)

Toxicity of common biocides used in aquaculture to embryos and larvae of Brachymystax tsinlingensis Li - Xing‐chen Guo; Zhi‐peng Chu; Rong‐qun Song; Zhen‐lu Wang; Rui‐jiao Li; Dong‐mei Xiong; Mu‐zi Zhang; Hai‐bo Jiang; Jian Shao (Journal of Fish Biology, 2024)
Brachymystax tsinlingensis Li is a threatened fish species endemic to China. With the problems of environmental factors and seeding breeding diseases, it is important to further improve the efficiency of seeding breeding and the basis of resource protection. This study investigated the acute toxicity of copper, zinc and methylene blue (MB) on hatching, survival, morphology, heart rate (HR) and stress behaviour of B. tsinlingensis . Eggs (diameter: 3.86 ± 0.07 mm, weight: 0.032 ± 0.004 g) of B. tsinlingensis were selected randomly from artificial propagation and developed from eye‐pigmentation‐stage embryos to yolk‐sac stage larvae (length: 12.40 ± 0.02 mm, weight: 0.03 ± 0.001 g) and exposed to different concentrations of Cu, Zn and MB for 144 h in a series of semi‐static toxicity tests. The acute toxicity tests indicated that the 96‐h median lethal concentration (LC 50 ) values of the embryos and larvae were 1.71 and 0.22 mg l −1 for copper and 2.57 and 2.72 mg l −1 for zinc, respectively, whereas the MB LC 50 after 144‐h exposure for embryos and larvae were 67.88 and 17.81 mg l −1 , respectively. The safe concentrations of copper, zinc and MB were 0.17, 0.77 and 6.79 mg l −1 for embryos and 0.03, 0.03 and 1.78 mg l −1 for larvae, respectively. Copper, zinc and MB treatments with concentrations greater than 1.60, 2.00 and 60.00 mg l −1 , respectively, led to a significantly low hatching rate and significantly high embryo mortality ( P −1 led to significantly high larvae mortality ( P P P B. tsinlingensis embryos or larvae might be more resistant to copper, zinc and MB than other members of the Salmonidae family, which benefits their resource protection and restoration.

Emergence and mobilization of a novel lincosamide resistance gene lnu(I): From environmental reservoirs to pathogenic bacteria - Zhishuang Yang; Tianjing Lan; Hongyan Luo; Pei Li; Mingshu Wang; Renyong Jia; Shun Chen; Mafeng Liu; Xinxin Zhao; Qiao Yang; Ying Wu; Shaqiu Zhang; et al. (Science of The Total Environment, 2024)

Constructing the covalent organic framework and In2O3 composites via covalent bonds towards excellent visible-light photocatalytic hydrogen evolution - Jungang Yi; Linfeng Zhang; Wei Wang; Qun Yi; Huadong Wu; Jianding Li; Jia Guo (Fuel, 2024)

Hypoxia-triggered tumor specific glutamine inhibition for reversing cisplatin resistance of chemotherapy - Jiaying Zhang; Jinghui Hu; Weiwei Zhu; Yurong Liu; Song Li; Haoting Chen; Fangling Liao; Qun Zhang; Xuan Sun; Xinting Li; Yafang Xiao; Jing Chen (Chemical Engineering Journal, 2024)

Detecting miRNA-21 using dual-mode biosensor via click chemistry-mediated variable temperature amplification reaction - Xiaofang Liu; Qun Wang; Ya Zhang; Zhihao Yang; Ning Li; Ying Xu; Mei Yang; Danqun Huo; Changjun Hou (Chemical Engineering Journal, 2024)

Fructooligosaccharides and fructans from Platycodon grandiflorum: Structural characterization, lung-oriented guidance and targetability - Jun Liang; Wen-Fei Wang; Yi Zhang; Yan-Qun Chai; Ya-Ge Li; Si-Liang Jiang; Xin-Hua Zhu; Yu-Li Guo; Zhen Wei; Xi-Zhe Sun; Hai-Xue Kuang; Yong-Gang Xia (Carbohydrate Polymers, 2024)

Interactions between CuO NPs and PS: The release of copper ions and oxidative damage - Yan Cao; Senlin Tian; Yingxue Geng; Linfeng Zhang; Qun Zhao; Jie Chen; Yingjie Li; Xuewei Hu; Jianhong Huang; Ping Ning (Science of The Total Environment, 2023)

Genome-wide identification and analysis of the MAPKK gene family in Chinese mitten crab (Eriocheir sinensis) and its response to bacterial challenge - Xiaona Zhang; Guoqing Shen; Yanan Guo; Xiaoli Zhang; Yuehong Zhao; Weiwei Li; Qun Wang; Yunlong Zhao (Fish & Shellfish Immunology, 2023)

Hyperoside Prevents Aβ42-Induced Neurotoxicity in PC12 Cells and Caenorhabditis elegans - Kexin Wang; Xinyue Zhang; Miaosi Zhang; Xin Li; Jiao Xie; Suwen Liu; Qun Huang; Jilite Wang; Qingbin Guo; Hao Wang (Molecular Neurobiology, 2023)

Projecting spatiotemporal dynamics of severe fever with thrombocytopenia syndrome in the mainland of China - Fang‐Yu Ding; Hong‐Han Ge; Tian Ma; Qian Wang; Meng‐Meng Hao; Hao Li; Xiao‐Ai Zhang; Richard James Maude; Li‐Ping Wang; Dong Jiang; Li‐Qun Fang; Wei Liu (Global Change Biology, 2023)
Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease with increasing incidence and geographic extent. The extent to which global climate change affects the incidence of SFTS disease remains obscure. We use an integrated multi‐model, multi‐scenario framework to assess the impact of global climate change on SFTS disease in China. The spatial distribution of habitat suitability for the tick Haemaphysalis longicornis was predicted by applying a boosted regression tree model under four alternative climate change scenarios (RCP2.6, RCP4.5, RCP6.0, and RCP8.5) for the periods 2030–2039, 2050–2059, and 2080–2089. We incorporate the SFTS cases in the mainland of China from 2010 to 2019 with environmental variables and the projected distribution of H. longicornis into a generalized additive model to explore the current and future spatiotemporal dynamics of SFTS. Our results demonstrate an expanded geographic distribution of H. longicornis toward Northern and Northwestern China, showing a more pronounced change under the RCP8.5 scenario. In contrast, the environmental suitability of H. longicornis is predicted to be reduced in Central and Eastern China. The SFTS incidence in three time periods (2030–2039, 2050–2059, and 2080–2089) is predicted to be increased as compared to the 2010s in the context of various RCPs. A heterogeneous trend across provinces, however, was observed, when an increased incidence in Liaoning and Shandong provinces, while decreased incidence in Henan province is predicted. Notably, we predict possible outbreaks in Xinjiang and Yunnan in the future, where only sporadic cases have been reported previously. These findings highlight the need for tick control and population awareness of SFTS in endemic regions, and enhanced monitoring in potential risk areas.

Enhancing degradation of organic matter in microbial electrolytic cells coupled with anaerobic digestion (MEC-AD) systems by carbon-based materials - Mengmeng Li; Qun Zhang; Yang Liu; Jiachen Zhu; Faqian Sun; Min-Hua Cui; He Liu; Tian C. Zhang; Chongjun Chen (Science of The Total Environment, 2023)

Widely targeted metabolomics provides insights into the effect of parboiling treatment on the nutritional quality of black rice based on its improved cooking characteristics - Xin Wu; Xingxing Zhang; Min Liu; Tang Tang; Yanhua Li; Hao Chen; Qun Lu; Rui Liu (Journal of Cereal Science, 2023)

Integration of hyperspectral imaging, non-targeted metabolomics and machine learning for vigour prediction of naturally and accelerated aged sweetcorn seeds - Tingting Zhang; Long Lu; Ni Yang; Ian D. Fisk; Wensong Wei; Li Wang; Jing Li; Qun Sun; Rensen Zeng (Food Control, 2023)

High efficient alkaline hydrogen evolution catalyzed by W2COx-Ru composite system containing bridged oxygen - Yu Dai; Hong Chuan Fu; Xiao Hui Chen; Qing Zhang; Ting Li; Nian Bing Li; Hong Qun Luo (Chemical Engineering Journal, 2023)

Investigation of Campbell mode with automatic calibration operated in fission chamber-based neutron flux monitoring system on EAST - Li Yang; Li-Qun Hu; Guo-Qiang Zhong; Hong-Rui Cao; Jin-Long Zhao; Yong-Qiang Zhang; Wei-Kun Chen (Annals of Nuclear Energy, 2023)

HVT-vectored H7 vaccine protects chickens from lethal infection with the highly pathogenic H7N9 Avian inﬂuenza virus - Yi-qun Chen; Guan-ming Su; Jia-hao Zhang; Bo Li; Kai-xiong Ma; Xu Zhang; Li-hong Huang; Ming Liao; Wen-bao Qi (Veterinary Microbiology, 2023)

The effect of microbial electrolysis cell coupled with anaerobic digestion for landfill leachate treatment - Mengmeng Li; Qun Zhang; Faqian Sun; Min-Hua Cui; He Liu; Chongjun Chen (Journal of Water Process Engineering, 2023)

A preliminary study of landslide dam failures induced by the combined influence of piping and overtopping - Chen Chen; Yanlong Wang; Jianmin Zhang; Han Zhang; Huanyun Li; Qun Chen (Journal of Hydrology, 2023)

Inventory of cadmium-transporter genes in the root of mangrove plant Avicennia marina under cadmium stress - Lu-Dan Zhang; Ling-Yu Song; Ming-Jin Dai; Jin-Yu Liu; Jing Li; Chao-Qun Xu; Ze-Jun Guo; Shi-Wei Song; Jing-Wen Liu; Xue-Yi Zhu; Hai-Lei Zheng (Journal of Hazardous Materials, 2023)

Establishment of protoplasts transient expression system in Pinellia ternata (Thunb.) Breit - Yu-hang Tian; Miao Liu; Liu Tang; Yu-jin Zhang; Ye Hang; Li-yang Shangguan; Yin-qun Zhang; Ming-sheng Zhang (Biotechnology Letters, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Co-pyrolysis characteristics of forestry and agricultural residues and waste plastics: Thermal decomposition and products distribution - Shuaihua Guo; Zhiwei Wang; Gaofeng Chen; Mengju Zhang; Tanglei Sun; Qun Wang; Zhimin Du; Yan Chen; Mengge Wu; Zaifeng Li; Tingzhou Lei; Kiran R.G. Burra; et al. (Process Safety and Environmental Protection, 2023)

Uncovering the virome and its interaction with antibiotic resistome during compost fertilization - Qingxia Zhang; Lei Zhou; Yilong Zhao; Shuhong Gao; Yanjun Yang; Qingyun Chen; Wenhui Li; Qi Qi; Qiang Dong; Jiesi Lei; Xue Guo; Qun Gao; et al. (Journal of Hazardous Materials, 2023)

Nutrient enrichment triggers contrasting sexual reproductive responses in native and invasive plants in a saltmarsh - Shiyun Qiu; Qun Zhang; Xiao Xu; Xincheng Li; Chenhao Zhou; Ji Yang; Wenneng Zhou; Bo Li (Journal of Cleaner Production, 2023)

A new xanthene-based platform for developing NIR fluorogenic probes for in vivo bioimaging - Xiao-Fan Zhang; Lin Shen; Sheng Wang; Qian Chen; Xiao-Qun Cao; Shi-Li Shen; Xiaohua Li (Chemical Engineering Journal, 2023)

Pyrroloquinoline quinone promotes growth and intestinal health and alleviates tris(1,3-dichloro-2-propyl) phosphate-induced hepatic oxidative stress in zebrafish - Chao-Qun Li; Yong-Jun Cao; Long-Fei Cui; Chun-Yang Zhang; Bei-Li Zhang; Qin-Yuan Ma (Aquaculture, 2023)

Targeted delivery of nutraceuticals derived from food for the treatment of obesity and its related complications - Zijian Dai; Yiyun Zhang; Yantong Meng; Siqi Li; Zhuoma Suonan; Yuge Sun; Junfu Ji; Qun Shen; Hao Zheng; Yong Xue (Food Chemistry, 2023)

Occurrence and risk assessment of organophosphate esters in global aquatic products - Luyao Gu; Boyuan Hu; Yilin Fu; Wei Zhou; Xiaomin Li; Kai Huang; Qun Zhang; Jie Fu; Haiyan Zhang; Aiqian Zhang; Jianjie Fu; Guibin Jiang (Water Research, 2023)

Immune functions of the Dscam extracellular variable region in Chinese mitten crab - Xiao-Li Zhang; Guo-Qing Shen; Xiao-Na Zhang; Yue-Hong Zhao; Wei-Wei Li; Qun Wang (Fish & Shellfish Immunology, 2023)

Unveiling the structure–activity relationships of ofloxacin degradation by Co3O4-activated peroxymonosulfate: From microstructures to exposed facets - Bo Li; Huan-Yan Xu; Yu-Long Liu; Yue Liu; Yan Xu; Si-Qun Zhang (Chemical Engineering Journal, 2023)

Modulating the interfacial built-in electric field in oxygen vacancies-enriched Ru/MxOy@C (M = V, Nb, Ta) ordered macroporous heterojunctions for electrocatalytic hydrogen production - Xiao Hui Chen; Hong Chuan Fu; Xiao Lin Li; Ting Li; Qing Zhang; Zi Qing Li; Yuan Hao Luo; Jing Lei Lei; Nian Bing Li; Hong Qun Luo (Chemical Engineering Journal, 2023)

Correction: Regulation of PPARγ/CPT-1 expression ameliorates cochlear hair cell injury by regulating cellular lipid metabolism and oxidative stress - Xiaorong Niu; Peng Han; Junsong Liu; Zichen Chen; Ting Zhang; Baiya Li; Xiaoyan Ma; Qun Wu; Xudong Ma (Molecular Genetics and Genomics, 2023)

In vivo cross-linking-based affinity purification and mass spectrometry for targeting intracellular protein-protein interactions - Bowen Zhong; Yuxin An; Hang Gao; Lili Zhao; Xiao Li; Zhen Liang; Yukui Zhang; Qun Zhao; Lihua Zhang (Analytica Chimica Acta, 2023)

Revisiting paleoenvironmental changes on the Upper Yangtze Block during the Ordovician-Silurian transition: New insights from elemental geochemistry - Zhen Qiu; Yifan Li; Wei Xiong; Tailiang Fan; Qun Zhao; Qin Zhang; Yuman Wang; Wen Liu; Feng Liang; Jiaqiang Zhang; Gary Lash (Sedimentary Geology, 2023)

ADGB variants cause asthenozoospermia and male infertility - Ronggui Qu; Zhihua Zhang; Ling Wu; Qun Li; Jian Mu; Lin Zhao; Zheng Yan; Wenjing Wang; Yang Zeng; Ruyi Liu; Jie Dong; Qiaoli Li; et al. (Human Genetics, 2023)

Deficiency of Lactoferrin aggravates lipopolysaccharide-induced acute inflammation via recruitment macrophage in mice - Can Liu; Qiu Peng; Lingyu Wei; Zhengshuo Li; Xiaoyue Zhang; Yangge Wu; Jia Wang; Xiang Zheng; Yuqing Wen; Run Zheng; Qun Yan; Qiurong Ye; et al. (BioMetals, 2023)

The effects of Chinese herbal feed additives on physiological health and detoxification ability in the red claw crayfish, Cherax quadricarinatus, and evaluation of their safety - Xiaohui Shi; Yongyi Jia; Zhuofan Zhang; Wenbo Wu; Zijie Wu; Meili Chi; Qun Zhao; Erchao Li (Aquaculture, 2023)

Deleting UL49.5 in duck plague virus causes attachment, entry and spread defects - Chunmei Li; Mingshu Wang; Anchun Cheng; Bin Tian; Juan Huang; Ying Wu; Qiao Yang; Qun Gao; Di Sun; Shaqiu Zhang; Xumin Ou; Sai Mao; et al. (Veterinary Microbiology, 2023)

Potential “downstream blocking” synergistic mechanism for urban warming in Kowloon Peninsula, Hong Kong - Cheng Zhang; Qun Wang; Pak Wai Chan; Yuguo Li (Urban Climate, 2023)

Performance of summertime temperature and wind fields under different background winds in Kowloon, Hong Kong - Cheng Zhang; Qun Wang; Pak Wai Chan; Yuguo Li (Urban Climate, 2023)

Antioxidant and anti-inflammatory activities of rape bee pollen after fermentation and their correlation with chemical components by ultra-performance liquid chromatography-quadrupole time of flight mass spectrometry-based untargeted metabolomics - Huifang Zhang; Xiaoling Zhu; Qian Huang; Li Zhang; Xiaohua Liu; Rui Liu; Qun Lu (Food Chemistry, 2023)

Single-cell-resolution transcriptome map revealed novel genes involved in testicular germ cell progression and somatic cells specification in Chinese tongue sole with sex reversal - Hong-Yan Wang; Xiang Liu; Jian-Yang Chen; Yingyi Huang; Yifang Lu; Fujian Tan; Qun Liu; Mingming Yang; Shuo Li; Xianghui Zhang; Yating Qin; Wenxiu Ma; et al. (Science China Life Sciences, 2023)

Responses of microbial community to geochemical parameters on vertical depth in bioheap system of low-grade copper sulfide - Xiu-Tong Li; Zhong-Sheng Huang; Ye Huang; Zhen Jiang; Zong-Lin Liang; Hua-Qun Yin; Guang-Ji Zhang; Yan Jia; Ye Deng; Shuang-Jiang Liu; Cheng-Ying Jiang (Science of The Total Environment, 2023)

Proteomic analysis reveals differential responsive mechanisms in Solanum nigrum exposed to low and high dose of cadmium - Ling-Yu Song; Xiang Liu; Lu-Dan Zhang; Wen-Jun Hu; Chao-Qun Xu; Jing Li; Shi-Wei Song; Ze-Jun Guo; Chen-Yang Sun; Han-Chen Tang; Ji-Cheng Wang; Xue-Yi Zhu; et al. (Journal of Hazardous Materials, 2023)

Life cycle assessment of bio-fermentation ethanol production and its influence in China's steeling industry - Lingyun Zhang; Qun Shen; Cheng Heng Pang; Wei Chao; Shuhuan Tong; Kien Woh Kow; Edward Lester; Tao Wu; Li Shang; Xuehang Song; Nannan Sun; Wei Wei (Journal of Cleaner Production, 2023)

Petrogenesis and Tectonic Implications of the Late Silurian–Early Devonian Bimodal Intrusive Rocks in the Central Beishan Orogenic Belt, NW China: Constraints by Petrology, Geochemistry and Hf Isotope - Jian Tian; Hou-Tian Xin; Xue-Jian Teng; Min Li; Qun-An Liao; Yong Zhang; Bang-Fang Ren (Journal of Earth Science, 2023)

A deep unrolling pansharpening method based on spectral consistency and double spatial priors - Dajiang Lei; Xin Luo; Hao Chen; Liping Zhang; Qun Liu; Weisheng Li (International Journal of Remote Sensing, 2023)

The mechanism of rh-endostatin-induced cardiotoxicity and its protection by dihydromyricetin[in vivo/in vitro, C57BL/6 mice, AC16 and hiPSC-CMs] - Xiaoran Guan; Wuquan Li; Yong Wang; Qun Zhao; Xinru Yu; Jing Jiang; Weihua Bian; Cong Xu; Yeying Sun; Chunxiang Zhang (Toxicology Letters, 2023)

Cascading effects of Pb on the environmental and symbiotic microbiota and tadpoles' physiology based on field data and laboratory validation - Wei Zhu; Yan Lv; Qun-De Zhang; Li-Ming Chang; Qi-Heng Chen; Bin Wang; Jian-Ping Jiang (Science of The Total Environment, 2023)

Deep learning drives efficient discovery of novel antihypertensive peptides from soybean protein isolate - Yiyun Zhang; Zijian Dai; Xinjie Zhao; Changyu Chen; Siqi Li; Yantong Meng; Zhuoma Suonan; Yuge Sun; Qun Shen; Liyang Wang; Yong Xue (Food Chemistry, 2023)

Fine mapping and candidate gene analysis of qFL-A12-5: a fiber length-related QTL introgressed from Gossypium barbadense into Gossypium hirsutum - Xianghui Xiao; Ruixian Liu; Juwu Gong; Pengtao Li; Ziyin Li; Wankui Gong; Aiying Liu; Qun Ge; Xiaoying Deng; Shaoqi Li; Quanjia Chen; Hua Zhang; et al. (Theoretical and Applied Genetics, 2023)

Regulation of PPARγ/CPT-1 expression ameliorates cochlear hair cell injury by regulating cellular lipid metabolism and oxidative stress - Xiaorong Niu; Peng Han; Junsong Liu; Zichen Chen; Ting Zhang; Baiya Li; Xiaoyan Ma; Qun Wu; Xudong Ma (Molecular Genetics and Genomics, 2023)

High-resolution, non-hydrostatic simulation of internal tides and solitary waves in the southern East China Sea - Wenjia Min; Qun Li; Zhenhua Xu; Yang Wang; Delei Li; Peiwen Zhang; Robin Robertson; Baoshu Yin (Ocean Modelling, 2023)

Developing strong and tough cellulose acetate/ZIF67 intelligent active films for shrimp freshness monitoring - Yan Zhang; Qun Tang; Kangqi Huang; Zongshu Xu; Shaoxiong Feng; Heping Li; Zhiming Zou (Carbohydrate Polymers, 2023)

A new acylated iridoid and other chemical constituents from Valeriana jatamansi and their biological activities - Yun Wang; Dao-Qun Shi; Na Jiang; Kai-Rui Rao; Shi-Xian Zhang; Dan Liu; Rong-Tao Li; Hong-Mei Li (Natural Product Research, 2023)

Dexamethasone affects the chemotaxis and phagocytic activity of neutrophils for boar spermatozoa and the quality of liquid preserved boar semen in vitro - Jing-Chun Li; Shuo Wang; He-Chuan Wang; Qun Zhang; Qian Wang; Ming-Hui Guo; Han Zhang; Tian-Feng Li; Qing Guo; Yan-Bing Li; Guo-Sheng Wei (Theriogenology, 2023)

One-step supramolecular construction of Lewis pair poly(ionic liquids) for atmospheric CO2 conversion to cyclic carbonates - Yuke Zhang; Mingyue Qiu; Jie Li; Haonan Wu; Lijuan Shi; Qun Yi (Fuel, 2023)

Integrinβ1/FAK/ERK signalling pathway is essential for Chinese mitten crab Eriocheir sinensis hemocyte survival - Yuehong Zhao; Xiaoli Zhang; Xiaona Zhang; Guoqing Shen; Weiwei Li; Qun Wang (Fish & Shellfish Immunology, 2023)

Deubiquitinase cylindromatosis (CYLD) regulates antibacterial immunity and apoptosis in Chinese mitten crab (Eriocheir sinensis) - Xiaona Zhang; Yuehong Zhao; Xiaoli Zhang; Guoqing Shen; Weiwei Li; Qun Wang (Fish & Shellfish Immunology, 2023)

Selective catalysis of single V atoms and VN1-x nanodots enables fast polysulfides conversion in lithium–sulfur batteries - Youquan Zhang; Cheng Ma; Chunxiao Zhang; Li Ma; Shuai Zhang; Qun Huang; Chaoping Liang; Libao Chen; Liangjun Zhou; Weifeng Wei (Chemical Engineering Journal, 2023)

Genome-wide association analyses of leaf rust resistance in cultivated emmer wheat - Dhondup Lhamo; Qun Sun; Qijun Zhang; Xuehui Li; Jason D. Fiedler; Guangmin Xia; Justin D. Faris; Yong-Qiang Gu; Upinder Gill; Xiwen Cai; Maricelis Acevedo; Steven S. Xu (Theoretical and Applied Genetics, 2023)

miR-200a-3p Regulates PRKACB and Participates in Aluminium-Induced Tau Phosphorylation in PC12 Cells - Huan Li; Qun Liu; Qinli Zhang; Xingli Xue; Jingsi Zhang; Jing Zhang; Li Lin; Qiao Niu (Neurotoxicity Research, 2022)
Aluminium (Al) is an environmental neurotoxin that humans are widely exposed to, but the molecular mechanism of its toxic effects is not fully understood. Many studies have shown that exposure to Al can cause abnormal phosphorylation of the tau protein that is believed as one of pathological features of Alzheimer’s disease. Increasing evidence indicates that microRNAs (miRNAs) may be involved in the pathological processes of neurodegenerative diseases and are potential regulatory factors for related target genes. Phosphorylation at Ser-133 of cAMP response element-binding protein (CREB) is one of the major pathways of CREB activation, and phosphorylation at this site is controlled by protein kinase A (PKA). The catalytic subunit of PKA, cAMP-dependent protein kinase catalytic subunit beta (PRKACB), phosphorylates CREB. The target gene prediction software TargetScan showed that PRKACB was one of the target mRNAs of miR-200a-3p. The purpose of this study was to investigate whether miR-200a-3p regulates the PKA/CREB pathway by targeting PRKACB and leads to abnormal phosphorylation of the tau protein in nerve cells. The results showed that Al exposure increased the expression level of miR-200a-3p, and miR-200a-3p increased the expression of targeted downregulated PRKACB, and then decreased the PKA/CREB signalling pathway activity, leading to abnormal hyperphosphorylation of tau. Graphical Abstract

STING/NF-κB/IL-6-Mediated Inflammation in Microglia Contributes to Spared Nerve Injury (SNI)-Induced Pain Initiation - Jia Sun; Ya-qun Zhou; Bing-yang Xu; Jia-yan Li; Long-qing Zhang; Dan-yang Li; Shuang Zhang; Jia-yi Wu; Shao-jie Gao; Da-wei Ye; Wei Mei (Journal of Neuroimmune Pharmacology, 2022)

An association study on the risk, glucocorticoids effectiveness, and prognosis of systemic lupus erythematosus: insight from mitochondrial DNA copy number - Zhen Li; Qi-Qun Zong; Chun-Xia Zhai; Guang-Hui Yu; Wan-Qin Hu; Yu-Hua Wang; Lin-Lin Wang; Zi-Ye Yan; Ting-Yu Zhang; Ying Teng; Shuang Liu; Jing Cai; et al. (Immunologic Research, 2022)

The role of ancestral seascape discontinuity and geographical distance in structuring rockfish populations in the Pacific Northwest - Cheng-He Sun; Rodolphe Elie Gozlan; Ting Wu; Dan Xue; Ye-Ling Lao; Jian-Feng Yu; Xiao-Shu Zeng; Sha Li; Emilie A. Hardouin; Demetra Andreou; Qun Zhang (Frontiers in Marine Science, 2022)
Despite the apparent absence of physical barriers in the ocean to prevent dispersal, recent studies have highlighted the importance of biological, geographical, physical, and historical barriers in the genetic structuring of marine species populations. This representation is essential for the sustainable exploitation of natural marine resources and for the setup of efficient protected area networks for the conservation of marine species. In this study, we used extensive sampling of Sebastiscus marmoratus , a commercially important inshore rockfish with high site fidelity, to characterize their population genetic structure along the China–Japan coast and to determine the effect of past geological and current biological–physical barriers on the current genetic footprint. A 461-bp fragment of the mtDNA hypervariable portion control region was sequenced for 675 individuals from 15 geographical locations. A total of 292 haplotypes were identified. The population of S. marmoratus showed high haplotype and nucleotide diversity. Pairwise fixation index ( F ST ) and analysis of molecular variance (AMOVA) revealed significant genetic differentiation among populations. The Bayesian skyline plots and neutrality statistics showed a sudden expansion of the S. marmoratus population around the Pleistocene. The Beibu Gulf group had the lowest mean number of pairwise differences, the lowest significant genetic differentiation, and the lowest haplotype and nucleotide diversity, and should be prioritized for protection in the future. Ocean currents, seascape discontinuity, geographical distance, and ecological characteristics may play an important role in shaping the contemporary phylogeographical patterns and population structures of S. marmoratus .

Survival virulent characteristics and transcriptomic analyses of Vibrio mimicus exposed to starvation - Ziyan Jiang; Shuwen Gu; Qieqi Qian; Jie Li; Peng Ji; Congcong Wu; Yingjie Zhang; Xiaojian Gao; Qun Jiang; Xiaojun Zhang (Frontiers in Marine Science, 2022)
Vibrio mimicus is a global causative agent of vibriosis in a variety of aquatic animals and causes major economic losses to aquaculture. It could survive in water for extended periods of time under environmental stress, but its survival strategy remains unknow. This study described the survival, virulent and gene expression changes of V. mimicus cells undergoing starvation stress. After 4 weeks’ cultivation in media without nutrients, V. mimicus Y4 showed reduced rates of activity with marked changes in morphology and physiological activities. The culturable cell counts declined gradually to 10 4 CFU/mL and the shape changed from rod-shaped to coccoid with short rods or spherical. The motility of starved cells decreased after starvation and the biofilm production was significantly lower than wild cells. The starved cells still produced β-hemolysis, lecithinase and caseinase, but its infectivity to Macrobrachium nipponense was weakened. To investigate the mechanism behind morphological and physiological changes, we further analyzed differently expressed genes (DEGs) between starved and wild cells at the whole transcriptional level. The RNA-seq analysis demonstrated that large-scale DEGs were involved in transferase, membrane, dehydrogenase, synthase, flagellar, hemolysin, pilus assembly, and starvation, etc. Among them, the well-known virulence-related genes were downregulated significantly, including vmh , pilA , vipA , capB , tadC , huvX , ompA , etc. These data provide a key resource to understand the regulatory mechanisms of V. mimicus to starvation stress.

Microbial succession and its effect on key aroma components during light-aroma-type Xiaoqu Baijiu brewing process - Bin Lin; Jie Tang; Qiang Yang; Zhixin Su; Liping Zhu; Qun Li; Wei Jiang; Long Zhang; Yuancai Liu; Shenxi Chen (World Journal of Microbiology and Biotechnology, 2022)

Phosphorylation of Truncated Tau Promotes Abnormal Native Tau Pathology and Neurodegeneration - Longfei Li; Yanli Jiang; Gang Wu; Yacoubou Abdoul Razak Mahaman; Dan Ke; Qun Wang; Bin Zhang; Jian-Zhi Wang; Hong-Lian Li; Rong Liu; Xiaochuan Wang (Molecular Neurobiology, 2022)

Facial emotion perception abilities are related to grey matter volume in the culmen of cerebellum anterior lobe in drug-naïve patients with first-episode schizophrenia - Xiaoxin Zhao; Jingjing Yao; Yiding Lv; Xinyue Zhang; Chongyang Han; Lijun Chen; Fangfang Ren; Qun Zhou; Zhuma Jin; Yuan Li; Yasong Du; Yuxiu Sui (Brain Imaging and Behavior, 2022)

The dysfunction of mGluRIIs is involved in the disorder of hippocampal neural network in diabetic mice model - Chunhua Liu; Qun Li; Zekang Wu; Shengwen Wang; Zhuo Yang; Tao Zhang (Experimental Brain Research, 2022)

Awareness for Endoscopic Screening Among Accompanying Children of Hospitalized Esophageal Cancer Patients in Henan - Lian Qun Zhang; Xian Juan Du; Fu You Zhou; Pei Nan Chen; Hai Ling Wang; Li Sun; Xiu Ling Li (Journal of Cancer Education, 2022)

Alterations to cognitive abilities and functional networks in rats post broad-band intense noise exposure - Xiao-Min Xu; Yu-Qun Zhang; Feng-Chao Zang; Chun-Qiang Lu; Li-Jie Liu; Jian Wang; Richard Salvi; Yu-Chen Chen; Gao-Jun Teng (Brain Imaging and Behavior, 2022)

White matter alterations in heart-kidney imbalance insomnia and Jiao-Tai-Wan treatment: A diffusion-tensor imaging study - Jie Chen; Yanxuan Li; Nengzhi Xia; Caiyun Wen; Tianyi Xia; Yuandi Zhuang; Mengmeng Jiang; Yilan Xiang; Mingyue Zhang; Chenyi Zhan; Yunjun Yang; Zhengzhong Yuan; et al. (Brain Imaging and Behavior, 2022)
Previous studies have reported changes in white matter microstructures in patients with insomnia. However, few neuroimaging studies have focused specifically on white matter tracts in insomnia patients after having received treatment. In this prospective study, diffusion-tensor imaging was used in two samples of heart-kidney imbalance insomnia patients who were treated with placebo or Jiao-Tai-Wan, a traditional Chinese medicine commonly used to treat heart-kidney imbalance insomnia, to assess the changes in white matter tracts. Tract-based spatial statistical analyses were first applied to compare the changes in mean diffusivity and fractional anisotropy of white matter between 75 heart-kidney imbalance insomnia patients and 41 healthy control participants. In subsequent randomized, double-blind, placebo-controlled trials, comparisons of mean diffusivity and fractional anisotropy were also performed in 24 heart-kidney imbalance insomnia patients (8 males; 16 females; 42.5 ± 10.4 years) with Jiao-Tai-Wan and 26 heart-kidney imbalance insomnia patients (11 males; 15 females; 39.7 ± 9.4 years) with a placebo, with age and sex as covariates. Fractional anisotropy values in left corticospinal tract were increased in heart-kidney imbalance insomnia patients. Heart-kidney imbalance insomnia patients showed lower mean diffusivity and fractional anisotropy values of several white matter tracts than healthy control participants, such as the bilateral anterior limb of internal capsule, bilateral superior longitudinal fasciculus and bilateral posterior corona radiata. After being treated with Jiao-Tai-Wan, heart-kidney imbalance insomnia patients showed a trend towards reduced fractional anisotropy values in the left corticospinal tract. Jiao-Tai-Wan may improve the sleep quality by reversing the structural changes of the left corticospinal tract caused by heart-kidney imbalance insomnia.

Depletion of B7-H4 from C3H10 T1/2 Mesenchymal Stem Cells Attenuates their Immunomodulatory Therapy in Experimental Autoimmune Encephalomyelitis Mice - Hao Li; Simao Sun; Zhou Yin; Shugang Cao; Xiaopei Ji; Xiaoyu Duan; Hanqing Gao; Mingyuan Wang; Qi Fang; Wanli Dong; Xueguang Zhang; Yanzheng Gu; et al. (Neurotoxicity Research, 2022)

Apigenin inhibits growth of melanoma by suppressing miR-512-3p and promoting the G1 phase of cell cycle involving the p27 Kip1 protein - Qun Xie; Ruirui Zhang; Dandan Liu; Jing Yang; Qiang Hu; Chao Shan; Xiaohan Li (Molecular and Cellular Biochemistry, 2022)

Internal solitary wave generation by the tidal flows beneath ice keel in the Arctic Ocean - Peiwen Zhang; Qun Li; Zhenhua Xu; Baoshu Yin (Journal of Oceanology and Limnology, 2022)

Characterization of Amphidinium (Amphidiniales, Dinophyceae) species from the China Sea based on morphological, molecular, and pigment data - Zhaohe Luo; Hua Zhang; Qun Li; Lei Wang; Hala F Mohamed; Songhui Lü; Haifeng Gu (Journal of Oceanology and Limnology, 2022)

Taxonomy and toxin profile of harmful benthic Prorocentrum (Dinophyceae) species from the Xisha Islands, South China Sea - Jian Zou; Qun Li; Hui Liu; Ying Liu; Lifen Huang; Haiyan Wu; Jiangbing Qiu; Hua Zhang; Songhui Lü (Journal of Oceanology and Limnology, 2022)

Observational Study on the Variability of Mixed Layer Depth in the Bering Sea and the Chukchi Sea in the Summer of 2019 - Xiaohui Jiao; Jicai Zhang; Qun Li; Chunyan Li (Frontiers in Marine Science, 2022)
Based on the CTD data from 58 stations in the Bering Sea and the Chukchi Sea in the summer of 2019, the values of mixed layer depth (MLD) were obtained by using the density difference threshold method. It was concluded that the MLD can be estimated more accurately by using a criterion of 0.125 kg/m 3 in this region. The average MLD in the Bering Sea basin was larger than that in the Bering Sea shelf, and both of them were smaller than that in the Bering Sea slope. The MLD increased northward in both the Chukchi Sea shelf and the Chukchi Sea slope. The farther northward, the greater the difference between the MLD calculated from temperature (MLDt) and the MLD calculated from density (MLDd). The water masses and their interaction played an important role in the variation of MLD in the northern Bering Sea shelf and Chukchi Sea. The MLD was large due to the vertically homogeneous Anadyr Water in the northwestern Bering Sea shelf. The horizontal advection of Bering Sea Anadyr Water and Alaska Coastal Water in the Bering Sea shelf led to shallower MLD in the central northern Bering Sea shelf. The westward advection of the Alaska Coastal Water caused shallow mixed layers (MLs) in some regions of the Chukchi Sea shelf in the summer of 2019. The observed large MLD at BL01 station near the Aleutian Island was caused by an anticyclonic eddy. The northward increase in the MLD in the Chukchi Sea was related to the low-salinity seawater from sea ice melting in summer. The spatial variation of MLD was also closely related to the surface momentum flux and the sea surface buoyancy flux. Stratification plays an even more important role in determining the variation of MLD. The ML in 2019 was shallower and warmer than those in previous years, especially in the Bering Sea shelf and Chukchi Sea where sea ice volume, thickness, and coverage were significantly larger than the Bering Sea basin, which was related to the small sea ice volume in winter and spring of 2019 compared to previous years.

Mitogenome of Knodus borki (Cypriniformes: Characidae): genomic characterization and phylogenetic analysis - Cheng-He Sun; Ya-Nan Zhang; Xiao-Shu Zeng; Da-Wei Liu; Qi Huang; Xiao-Li Zhang; Qun Zhang (Molecular Biology Reports, 2022)

Radical chemistry of dissolved black carbon under sunlight irradiation: quantum yield prediction and effects on sulfadiazine photodegradation - Yina Tu; Huaying Liu; Yingjie Li; Zhiyu Zhang; Yajie Lei; Qun Zhao; Senlin Tian (Environmental Science and Pollution Research, 2022)

Identification and analysis of oil candidate genes reveals the molecular basis of cottonseed oil accumulation in Gossypium hirsutum L. - Zhibin Zhang; Juwu Gong; Zhen Zhang; Wankui Gong; Junwen Li; Yuzhen Shi; Aiying Liu; Qun Ge; Jingtao Pan; Senmiao Fan; Xiaoying Deng; Shaoqi Li; et al. (Theoretical and Applied Genetics, 2022)

Fractal analysis of root architecture responses of Saussurea salsa to a gradient of flooding intensity and salinity - Qun Li; Cheng-Zhang Zhao; Jun Wen; Manping Kang; Xiaoya Li (Plant and Soil, 2022)

Mesenchymal-to-epithelial transition of osteoblasts induced by Fam20c knockout - Ya-Wei Geng; Zhen Zhang; Han Jin; Jun-Long Da; Kai Zhang; Jian-Qun Wang; Yu-Yao Guo; Bin Zhang; Ying Li (Genes & Genomics, 2022)

Lathyrane diterpenoids from Jatropha podagrica and their antitumor activities in human osteosarcoma cells - Han-Tao Yuan; Qun-Feng Li; Tian Tian; Chun-Yan Zhang; Zou-Qin Huang; Chun-Xiang Fan; Ke Mei; Jie Zhou; Xiao-Xiang Zhai; Si-Bo Li; Jian-Yong Zhu (Natural Product Research, 2021)

Influence of loading rates under true triaxial stress on the mechanical properties and rockburst characteristics of granite - Zhanjin Li; Lu Zhang; Qun Li; Haojie Cheng (Arabian Journal of Geosciences, 2021)

Effects of temperature on the growth and carbohydrate production of three benthic dinoflagellate species from Hainan Island, South China Sea - Zhen Wu; Hua Zhang; Qun Li; Lei Cui; Heng Chen; Songhui Lu (Ecotoxicology, 2021)

Functional analysis of indole 3-hexanoic acid as a novel auxin from Arabidopsis thaliana - Ping Song; Hui Xu; Jixiu Zhang; Huatao Chen; Li Li; Yana Qu; Feng Lin; Qun Zhang (Planta, 2021)

Aspergillus fumigatus Induces the Release of IL-8 and MCP-1 by Activating Nuclear Transcription Through Dectin-1 and CR3 Receptors in Alveolar Epithelial Cells - Yanxi Liu; Zhiqian Li; Shuo Wang; Changjian Zhang; Li Han; Qun Sun; Xuelin Han (Current Microbiology, 2021)

Characterization, Sources and Excessive Cancer Risk of PM2.5-Bound Polycyclic Aromatic Hydrocarbons in Different Green Spaces in Lin’an, Hangzhou, China - Fang Huang; Yinke Zhang; Yilei Lou; Xiaolu Li; Tianran Zhang; Hui Yu; Chuyang Yuan; Qun Tong; Feng Qi; Feng Shao (Bulletin of Environmental Contamination and Toxicology, 2021)

Enhanced Biodegradation of Hexachlorocyclohexane in Soil by Application of Exogenous Amendments - Xutong Liu; He Huang; Dan Huang; Kai Zhong; Qun Rong; Xingzi Qin; Chaolan Zhang; Xue Li (Water, Air, & Soil Pollution, 2021)

Using the Metabolome to Understand the Mechanisms Linking Chronic Arsenic Exposure to Microglia Activation, and Learning and Memory Impairment - Rui-Yuan Zhang; Jie-Bai Tu; Rui-Tu Ran; Wen-Xuan Zhang; Qiang Tan; Ping Tang; Tao Kuang; Shu-Qun Cheng; Cheng-Zhi Chen; Xue-Jun Jiang; Chang Chen; Ting-Li Han; et al. (Neurotoxicity Research, 2021)

Morphology and molecular phylogeny of three species of Coolia (Dinophyceae) from Hainan Island, South China Sea - Hua Zhang; Songhui Lü; Jingyi Cen; Yang Li; Qun Li; Zhen Wu (Journal of Oceanology and Limnology, 2021)

Flavonoids repress the production of antifungal 2, 4‐DAPG but potentially facilitate root colonization of the rhizobacterium Pseudomonas fluorescens - Xiao‐Quan Yu; Xu Yan; Meng‐Yuan Zhang; Li‐Qun Zhang; Yong‐Xing He (Environmental Microbiology, 2020)
Summary In the well‐known legume–rhizobia symbiosis, flavonoids released by legume roots induce expression of the Nod factors and trigger early plant responses involved in root nodulation. However, it remains largely unknown how the plant‐derived flavonoids influence the physiology of non‐symbiotic beneficial rhizobacteria. In this work, we demonstrated that the flavonoids apigenin and/or phloretin enhanced the swarming motility and production of cellulose and curli in Pseudomonas fluorescens 2P24, both traits of which are essential for root colonization. Using a label‐free quantitative proteomics approach, we showed that apigenin and phloretin significantly reduced the biosynthesis of the antifungal metabolite 2,4‐DAPG and further identified a novel flavonoid‐sensing TetR regulator PhlH, which was shown to modulate 2,4‐DAPG production by regulating the expression of 2,4‐DAPG hydrolase PhlG. Although having similar structures, apigenin and phloretin could also influence different physiological characteristics of P . fluorescens 2P24, with apigenin decreasing the biofilm formation and phloretin inducing expression of proteins involved in the denitrification and arginine fermentation processes. Taken together, our results suggest that plant‐derived flavonoids could be sensed by the TetR regulator PhlH in P . fluorescens 2P24 and acts as important signalling molecules that strengthen mutually beneficial interactions between plants and non‐symbiotic beneficial rhizobacteria.

Phosphodiesterase 2 inhibitor Hcyb1 reverses corticosterone-induced neurotoxicity and depression-like behavior - Meng-Jia Zhu; Jing Shi; Yong Chen; Guobing Huang; Xiong-Wei Zhu; Sam Zhang; Xian-Feng Huang; Guo-Qiang Song; Han-Ting Zhang; Heng-Ming Ke; James M. O’Donnell; Li-Qun Wang; et al. (Psychopharmacology, 2020)

The effect of blastomere loss during frozen embryo transfer on the transcriptome of offspring’s umbilical cord blood - Yan-Ting Wu; Ze-Han Dong; Cheng Li; Dai-Zhan Zhou; Jun-Yu Zhang; Yan Wu; Jing-Jing Xu; Yu Wang; Xiao-Qun Ye; Jian-Zhong Sheng; Li Wang; He-Feng Huang (Molecular Biology Reports, 2020)

Enhancement of protoplast preparation and regeneration of Hirsutella sinensis based on process optimization - Li-Qun Jin; Zhe-Wen Xu; Xiao-Hui Men; Bo-Zhang; Zhi-Qiang Liu; Yu-Guo Zheng (Biotechnology Letters, 2020)

Comparative Pharmacokinetics of Nimodipine in Rat Plasma and Tissues Following Intraocular, Intragastric, and Intravenous Administration - Fang Li; Qingsong Fei; Dan Mao; Qiaoyun Si; Manman Dai; Qun Ma; Huimin Zhang; Luyu Bai; Ning He (AAPS PharmSciTech, 2020)

Examining two sets of introgression lines across multiple environments reveals background-independent and stably expressed quantitative trait loci of fiber quality in cotton - Yuzhen Shi; Aiying Liu; Junwen Li; Jinfa Zhang; Shaoqi Li; Jinfeng Zhang; Liujun Ma; Rui He; Weiwu Song; Lixue Guo; Quanwei Lu; Xianghui Xiang; et al. (Theoretical and Applied Genetics, 2020)
Key message Background-independent (BI) and stably expressed (SE) quantitative trait loci (QTLs) were identified using two sets of introgression lines across multiple environments. Genetic background more greatly affected fiber quality traits than environmental factors. Sixty-one SE-QTLs, including two BI-QTLs, were novel and 48 SE-QTLs, including seven BI-QTLs, were previously reported. Abstract Cotton fiber quality traits are controlled by QTLs and are susceptible to environmental influence. Fiber quality improvement is an essential goal in cotton breeding but is hindered by limited knowledge of the genetic basis of fiber quality traits. In this study, two sets of introgression lines of Gossypium hirsutum × G. barbadense were used to dissect the QTL stability of three fiber quality traits (fiber length, strength and micronaire) across environments using 551 simple sequence repeat markers selected from our high-density genetic map. A total of 76 and 120 QTLs were detected in the CCRI36 and CCRI45 backgrounds, respectively. Nine BI-QTLs were found, and 78 (41.71%) of the detected QTLs were reported previously. Thirty-nine and 79 QTLs were SE-QTLs in at least two environments in the CCRI36 and CCRI45 backgrounds, respectively. Forty-eight SE-QTLs, including seven BI-QTLs, were confirmed in previous reports, and 61 SE-QTLs, including two BI-QTLs, were considered novel. These results indicate that genetic background more strongly impacts on fiber quality traits than environmental factors. Twenty-three clusters with BI- and/or SE-QTLs were identified, 19 of which harbored favorable alleles from G. barbadense for two or three fiber quality traits. This study is the first report using two sets of introgression lines to identify fiber quality QTLs across environments in cotton, providing insights into the effect of genetic backgrounds and environments on the QTL expression of fiber quality and important information for the genetic basis underlying fiber quality traits toward QTL cloning and molecular breeding.

Late Pleistocene environmental information on the Diexi paleo-dammed lake of the upper Minjiang River in the eastern margin of the Tibetan Plateau, China - Lan-sheng Wang; Xiao-qun Wang; Jun-hui Shen; Guan Yin; Jie Cui; Xiang-ning Xu; Zhi-long Zhang; Tao Wan; Li-wang Wen (Journal of Mountain Science, 2020)

Dissecting the genetic basis of fiber quality and yield traits in interspecific backcross populations of Gossypium hirsutum × Gossypium barbadense - Yuzhen Shi; Aiying Liu; Junwen Li; Jinfa Zhang; Baocai Zhang; Qun Ge; Muhammad Jamshed; Quanwei Lu; Shaoqi Li; Xianghui Xiang; Juwu Gong; Wankui Gong; et al. (Molecular Genetics and Genomics, 2019)

The complete chloroplast genome of the daimyo oak, Quercus dentata Thunb. - Hua-Lei Hu; Jing-Yu Zhang; Yu-Ping Li; Lu Xie; Dong-Bin Chen; Qun Li; Yan-Qun Liu; Shu-Rong Hui; Li Qin (Conservation Genetics Resources, 2019)

Osteological evidence of violence during the formation of the Chinese northern nomadic cultural belt in the Bronze Age - Qun Zhang; Xuezhou Li; Qian Wang; Hui-Yuan Yeh; Hong Zhu; Yanguo Qin; Quanchao Zhang (Archaeological and Anthropological Sciences, 2019)

In situ meta‐omic insights into the community compositions and ecological roles of hadal microbes in the Mariana Trench - Zhao‐Ming Gao; Jiao‐Mei Huang; Guo‐Jie Cui; Wen‐Li Li; Jun Li; Zhan‐Fei Wei; Jun Chen; Yong‐Zhi Xin; Du‐Si Cai; Ai‐Qun Zhang; Yong Wang (Environmental Microbiology, 2019)
Summary The low temperature and elevated hydrostatic pressure in hadal trenches at water depths below 6000 m render sample collection difficult. Here, in situ hadal water microbial samples were collected from the Mariana Trench and analysed. The hadal microbial communities at different depths were revealed to be consistent and were dominated by heterotrophic Marinimicrobia. Thirty high‐quality metagenome‐assembled genomes (MAGs) were retrieved to represent the major hadal microbes affiliated with 12 prokaryotic phyla. Most of the MAGs were newly reported and probably derived from novel hadal inhabitants as exemplified by a potentially new candidate archaeal phylum in the DPANN superphylum. Metabolic reconstruction indicated that a great number of the MAGs participated in nitrogen and sulfur cycling, in which the nitrification process was driven sequentially by Thaumarchaeota and Nitrospirae and sulfur oxidization by Rhodospirillales in the Alphaproteobacteria class. Moreover, several groups of hadal microbes were revealed to be potential carbon monoxide oxidizers. Metatranscriptomic result highlighted the contribution of Chloroflexi in degrading recalcitrant dissolved organic matter and Marinimicrobia in extracellular protein decomposition. The present work provides an in‐depth view on the hadal microbial communities regarding their endemism and element cycles.

QTL mapping and genetic effect of chromosome segment substitution lines with excellent fiber quality from Gossypium hirsutum × Gossypium barbadense - Shao-qi Li; Ai-ying Liu; Ling-lei Kong; Ju-wu Gong; Jun-wen Li; Wan-kui Gong; Quan-wei Lu; Peng-tao Li; Qun Ge; Hai-hong Shang; Xiang-hui Xiao; Rui-xian Liu; et al. (Molecular Genetics and Genomics, 2019)

Exploratory of immobilization remediation of hydroxyapatite (HAP) on lead-contaminated soils - Yifan Wang; Ruizhen Li; Wenzhu Liu; Li Cheng; Qun Jiang; Ying Zhang (Environmental Science and Pollution Research, 2019)

Half-dose ticagrelor versus high-dose clopidogrel in reducing platelet reactivity in acute coronary syndrome patients with high on-clopidogrel platelet reactivity (divide study) - Guang Zhong Liu; Song Zhang; Dang Hui Sun; Jing Shi; Wan Lan Bo; Wen Nan Wang; Chong Yang Zhang; Zhong Hua Wang; Wei Feng; Mei Jiao He; Yuan Yuan Liu; Shuang Li; et al. (European Journal of Clinical Pharmacology, 2019)

Alleviation of atrazine toxicity to maize seedlings grown in soils with amendment of biochar derived from wheat under different temperatures - Yifan Wang; Yi Tang; Qun Jiang; Xinyuan Zhang; Weiling Xie; Ruizhen Li; Wenzhu Liu; Jiaming Kang; Ying Zhang (Environmental Science and Pollution Research, 2019)

Quantitative trait locus mapping for plant height and branch number in an upland cotton recombinant inbred line with an SNP-based high-density genetic map - Zhen Zhang; Aiying Liu; Zhen Huang; Senmiao Fan; Xianyan Zou; Xiaoying Deng; Qun Ge; Juwu Gong; Junwen Li; Wankui Gong; Yuzhen Shi; Liqiang Fan; et al. (Euphytica, 2019)

Rescue and characterization of a recombinant HY12 bovine enterovirus carrying a foreign HA epitope in the 3A nonstructural protein - Dan Liu; Changming Liu; Xing Liu; Xin Li; Liping Huang; Junying Hu; Yanwu Wei; Hongzhen Zhu; Qun Zhang; Xinping Wang (Archives of Virology, 2019)

A numerical simulation of the generation and evolution of nonlinear internal waves across the Kara Strait - Qun Li; Huiding Wu; Hongwei Yang; Zhanhai Zhang (Acta Oceanologica Sinica, 2019)

The antitoxin MqsA homologue in Pseudomonas fluorescens 2P24 has a rewired regulatory circuit through evolution - Yong Wang; Si‐Ping Zhang; Meng‐Yuan Zhang; Megan L. Kempher; Ding‐Ding Guo; Jian‐Ting Han; Xuanyu Tao; Yi Wu; Li‐Qun Zhang; Yong‐Xing He (Environmental Microbiology, 2019)
Summary The mqsRA operon encodes a toxin–antitoxin pair that was characterized to participate in biofilm and persister cell formation in Escherichia coli . Notably, the antitoxin MqsA possesses a C‐terminal DNA‐binding domain that recognizes the [5’‐AACCT(N) 2‐4 AGGTT‐3′] motif and acts as a transcriptional regulator controlling multiple genes including the general stress response regulator RpoS. However, it is unknown how the transcriptional circuits of MqsA homologues have changed in bacteria over evolutionary time. Here, we found mqsA in Pseudomonas fluorescens ( PfmqsA ) is acquired through horizontal gene transfer and binds to a slightly different motif [5′‐TACCCT(N) 3 AGGGTA‐3′], which exists upstream of the PfmqsRA operon. Interestingly, an adjacent GntR‐type transcriptional regulator, which was termed AgtR, is under negative control of PfMqsA. It was further demonstrated that PfMqsA reduces production of biofilm components through AgtR, which directly regulates the pga and fap operons involved in the synthesis of extracellular polymeric substances. Moreover, through quantitative proteomics analysis, we showed AgtR is a highly pleiotropic regulator that influences up to 252 genes related to diverse processes including chemotaxis, oxidative phosphorylation and carbon and nitrogen metabolism. Taken together, our findings suggest the rewired regulatory circuit of PfMqsA influences diverse physiological aspects of P. fluorescens 2P24 via the newly characterized AgtR.

Secondary metabolites from Antarctic marine-derived fungus Penicillium crustosum HDN153086 - Cong-Cong Liu; Zhen-Zhen Zhang; Yan-Yan Feng; Qian-Qun Gu; De-Hai Li; Tian-Jiao Zhu (Natural Product Research, 2019)

Genomics insights into ecotype formation of ammonia‐oxidizing archaea in the deep ocean - Yong Wang; Jiao‐Mei Huang; Guo‐Jie Cui; Takuro Nunoura; Yoshihiro Takaki; Wen‐Li Li; Jun Li; Zhao‐Ming Gao; Ken Takai; Ai‐Qun Zhang; Ramunas Stepanauskas (Environmental Microbiology, 2019)
Summary Various lineages of ammonia‐oxidizing archaea (AOA) are present in deep waters, but the mechanisms that determine ecotype formation are obscure. We studied 18 high‐quality genomes of the marine group I AOA lineages (alpha, gamma and delta) from the Mariana and Ogasawara trenches. The genomes of alpha AOA resembled each other, while those of gamma and delta lineages were more divergent and had even undergone insertion of some phage genes. The instability of the gamma and delta AOA genomes could be partially due to the loss of DNA polymerase B ( polB) and methyladenine DNA glycosylase ( tag ) genes responsible for the repair of point mutations. The alpha AOA genomes harbour genes encoding a thrombospondin‐like outer membrane structure that probably serves as a barrier to gene flow. Moreover, the gamma and alpha AOA lineages rely on vitamin B 12 ‐independent MetE and B 12 ‐dependent MetH, respectively, for methionine synthesis. The delta AOA genome contains genes involved in uptake of sugar and peptide perhaps for heterotrophic lifestyle. Our study provides insights into co‐occurrence of cladogenesis and anagenesis in the formation of AOA ecotypes that perform differently in nitrogen and carbon cycling in dark oceans.

Role of AGEs in the progression and regression of atherosclerotic plaques - Zhong-qun Wang; Le-le Jing; Jin-chuan Yan; Zhen Sun; Zheng-yang Bao; Chen Shao; Qi-wen Pang; Yue Geng; Li-li Zhang; Li-hua Li (Glycoconjugate Journal, 2018)

Genomics‐driven discovery of a novel self‐resistance mechanism in the echinocandin‐producing fungus Pezicula radicicola - Qun Yue; Yan Li; Li Chen; Xiaoling Zhang; Xingzhong Liu; Zhiqiang An; Gerald F Bills (Environmental Microbiology, 2018)
Summary The echinocandins are antifungal lipopeptides targeting fungi via noncompetitive inhibition of the β‐1,3‐ d ‐glucan synthase FKS1 subunit. A novel echinocandin resistance mechanism involving an auxiliary copy of FKS1 in echinocandin‐producing fungus Pezicula radicicola NRRL 12192 was discovered. We sequenced the genome of NRRL 12192 and predicted two FKS1‐encoding genes ( prfks1n and prfks1a ), rather than a single FKS1 gene typical of filamentous ascomycetes. The prfks1a gene sits immediately adjacent to an echinocandin (sporiofungin) gene cluster, which was confirmed by disruption of prnrps4 and abolishment of sporiofungin production. Disruption of prfks1a dramatically increased the strain's sensitivity to exogenous echinocandins. In the absence of echinocandins, transcription levels of prfks1a relative to β ‐tubulin in the wild type and in Δ prnrps4 stains were similar. Moreover, prfks1a is consistently transcribed at low levels and is upregulated in the presence of exogenous echinocandin, but not during growth conditions promoting endogenous production of sporiofungin. Therefore, we conclude that prfks1a is primarily responsible for protecting the fungus against extracellular echinocandin toxicity. The presence of unclustered auxiliary copies of FKS1 with high similarity to prfks1a in two other echinocandin‐producing strains suggests that this previously unrecognized resistance mechanism may be common in echinocandin‐producing fungi of the family Dermataceae of the class Leotiomycetes.

Gut Microbiota and its Modulation for Healthy Farming of Pacific White Shrimp Litopenaeus vannamei - Erchao Li; Chang Xu; Xiaodan Wang; Shifeng Wang; Qun Zhao; Meiling Zhang; Jian G. Qin; Liqiao Chen (Reviews in Fisheries Science & Aquaculture, 2018)

Alterations in Normal Aging Revealed by Cortical Brain Network Constructed Using IBASPM - Wan Li; Chunlan Yang; Feng Shi; Qun Wang; Shuicai Wu; Wangsheng Lu; Shaowu Li; Yingnan Nie; Xin Zhang (Brain Topography, 2018)

High-density genetic map construction and QTL mapping for fiber strength on Chr24 across multiple environments in a CCRI70 recombinant inbred lines population - Xianyan Zou; Juwu Gong; Li Duan; Xiao Jiang; Zhang Zhen; Senmiao Fan; Qun Ge; Aiying Liu; Wankui Gong; Junwen Li; Yuzhen Shi; Yanling Wang; et al. (Euphytica, 2018)

Permutation Mutual Information: A Novel Approach for Measuring Neuronal Phase-Amplitude Coupling - Ning Cheng; Qun Li; Sitong Wang; Rubin Wang; Tao Zhang (Brain Topography, 2018)

A statistical distribution of quad-pol X-band sea clutter time series acquired at a grazing angle - Yunhua Wang; Qun Li; Yanmin Zhang (Acta Oceanologica Sinica, 2018)

A novel Scan SAR imaging method for maritime surveillance via L p regularization - Jia-cheng Ni; Qun Zhang; Yu-fu Yin; Ying Luo; Li Sun (International Journal of Remote Sensing, 2018)

Gender-Related Hippocampal Proteomics Study from Young Rats After Chronic Unpredicted Mild Stress Exposure - Lin-Na Ning; Teng Zhang; Jiang Chu; Na Qu; Li Lin; Ying-Yan Fang; Yan Shi; Peng Zeng; Er-Li Cai; Xiao-Ming Wang; Qun Wang; You-Ming Lu; et al. (Molecular Neurobiology, 2018)

Comorbidity Burden of Dementia: A Hospital-Based Retrospective Study from 2003 to 2012 in Seven Cities in China - Qing-Hua Wang; Xin Wang; Xian-Le Bu; Yan Lian; Yang Xiang; Hong-Bo Luo; Hai-Qiang Zou; Jie Pu; Zhong-He Zhou; Xiao-Ping Cui; Qing-Song Wang; Xiang-Qun Shi; et al. (Neuroscience Bulletin, 2017)

Involvement of IL-17 in Secondary Brain Injury After a Traumatic Brain Injury in Rats - Tan Li; Yong-mei Zhang; Dong Han; Rong Hua; Bing-nan Guo; Shu-qun Hu; Xian-liang Yan; Tie Xu (NeuroMolecular Medicine, 2017)

Structural Transformation Detection Contributes to Screening of Behaviorally Active Compounds: Dynamic Binding Process Analysis of DhelOBP21 from Dastarcus helophoroides - Rui-Nan Yang; Dong-Zhen Li; Guangqiang Yu; Shan-Cheng Yi; Yinan Zhang; De-Xin Kong; Man-Qun Wang (Journal of Chemical Ecology, 2017)

Nortirucallane A, a new tirucallane-type nortriterpenoid isolated from Lonicerae japonicae flos - Xu Wang; Jing Zhang; Ya-qun Li; Bao-xiang Du; Qi-hui Sun; Yun-jiao Cao; Hai-qiang Jiang; Yu-hong Liu; Hong-lei Zhou; Rong Rong (Natural Product Research, 2017)

Tbx18-dependent differentiation of brown adipose tissue-derived stem cells toward cardiac pacemaker cells - Lei Chen; Zi-Jun Deng; Jian-Sheng Zhou; Rui-Juan Ji; Xi Zhang; Chuan-Sen Zhang; Yu-Quan Li; Xiang-Qun Yang (Molecular and Cellular Biochemistry, 2017)

Molecular identification of differential expression genes associated with sex pheromone biosynthesis in Spodoptera exigua - Ya-Nan Zhang; Long-Wa Zhang; Da-Song Chen; Liang Sun; Zhao-Qun Li; Zhan-Feng Ye; Mei-Yan Zheng; Jin-Bu Li; Xiu-Yun Zhu (Molecular Genetics and Genomics, 2017)

Climatic and geographic factors affect ecosystem multifunctionality through biodiversity in the Tibetan alpine grasslands - Ying Pan; Jun-xi Wu; Li-ming Luo; Yan-li Tu; Cheng-qun Yu; Xian-zhou Zhang; Yan-jun Miao; Yan Zhao; Jun-ling Yang (Journal of Mountain Science, 2017)

Impact of land use conversion on soil organic carbon stocks in an agro-pastoral ecotone of Inner Mongolia - Wei Zhao; Zhongmin Hu; Shenggong Li; Qun Guo; Hao Yang; Tonghui Zhang (Journal of Geographical Sciences, 2017)

Anti-hepatocarcinoma activity of TT-1, an analog of melittin, combined with interferon-α via promoting the interaction of NKG2D and MICA - Lan-lan Wan; Da-qi Zhang; Jin-nan Zhang; Li-qun Ren (Journal of Zhejiang University-SCIENCE B, 2017)

Effect of annexin A7 suppression on the apoptosis of gastric cancer cells - Weihua Ye; Yong Li; Liqiao Fan; Qun Zhao; Hufang Yuan; Bibo Tan; Zhidong Zhang (Molecular and Cellular Biochemistry, 2017)

Adenosine A2A receptors in the olfactory bulb suppress rapid eye movement sleep in rodents - Yi-Qun Wang; Rui Li; Dian-Ru Wang; Yoan Cherasse; Ze Zhang; Meng-Qi Zhang; Oriana Lavielle; Kristopher McEown; Serge N. Schiffmann; Alban de Kerchove d’Exaerde; Wei-Min Qu; Michael Lazarus; et al. (Brain Structure and Function, 2017)

Ecotoxicological bioassays of sediment leachates in a river bed flanked by decommissioned pesticide plants in Nantong City, East China - Yan Zhou; Fenghe Wang; Jinzhong Wan; Jian He; Qun Li; Qiang Chen; Jay Gao; Yusuo Lin; Shengtian Zhang (Environmental Science and Pollution Research, 2017)

Identification and Characterization of the Lysine-Rich Matrix Protein Family in Pinctada fucata: Indicative of Roles in Shell Formation - Jian Liang; Jun Xie; Jing Gao; Chao-Qun Xu; Yi Yan; Gan-Chu Jia; Liang Xiang; Li-Ping Xie; Rong-Qing Zhang (Marine Biotechnology, 2016)

Augmented expression of gamma-glutamyl transferase 5 (GGT5) impairs testicular steroidogenesis by deregulating local oxidative stress - Wei Li; Zhi-qun Wu; Shun Zhang; Rui Cao; Jie Zhao; Zhi-jian Sun; Wei Zou (Cell and Tissue Research, 2016)

Glutathione improves survival of cryopreserved embryogenic calli of Agapanthus praecox subsp. orientalis - Guan-qun Chen; Li Ren; Di Zhang; Xiao-hui Shen (Acta Physiologiae Plantarum, 2016)

Genomic characterization of symbiotic mycoplasmas from the stomach of deep‐sea isopod bathynomus sp - Yong Wang; Jiao‐Mei Huang; Shao‐Lu Wang; Zhao‐Ming Gao; Ai‐Qun Zhang; Antoine Danchin; Li‐Sheng He (Environmental Microbiology, 2016)
Deep‐sea isopod scavengers such as Bathynomus sp. are able to live in nutrient‐poor environments, which is likely attributable to the presence of symbiotic microbes in their stomach. In this study we recovered two draft genomes of mycoplasmas, Bg1 and Bg2, from the metagenomes of the stomach contents and stomach sac of a Bathynomus sp. sample from the South China Sea (depth of 898 m). Phylogenetic trees revealed a considerable genetic distance to other mycoplasma species for Bg1 and Bg2. Compared with terrestrial symbiotic mycoplasmas, the Bg1 and Bg2 genomes were enriched with genes encoding phosphoenolpyruvate‐dependent phosphotransferase systems (PTSs) and sodium‐driven symporters responsible for the uptake of sugars, amino acids and other carbohydrates. The genome of mycoplasma Bg1 contained sialic acid lyase and transporter genes, potentially enabling the bacteria to attach to the stomach sac and obtain organic carbons from various cell walls. Both of the mycoplasma genomes contained multiple copies of genes related to proteolysis and oligosaccharide degradation, which may help the host survive in low‐nutrient conditions. The discovery of the different types of mycoplasma bacteria in the stomach of this deep‐sea isopod affords insights into symbiotic model of deep‐sea animals and genomic plasticity of mycoplasma bacteria.

Rutaecarpine attenuates hypoxia-induced right ventricular remodeling in rats - Wen-Qun Li; Xiao-Hui Li; Jie Du; Wang Zhang; Dai Li; Xiao-Ming Xiong; Yuan-Jian Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Two generalized algorithms measuring phase–amplitude cross-frequency coupling in neuronal oscillations network - Qun Li; Chen-guang Zheng; Ning Cheng; Yi-yi Wang; Tao Yin; Tao Zhang (Cognitive Neurodynamics, 2016)

Hepatitis B virus genotype A: design of reference sequences for sub-genotypes - Qun Cai; Huilan Zhu; Yafei Zhang; Xu Li; Zhenhua Zhang (Virus Genes, 2016)

Genomic and physiological analysis reveals versatile metabolic capacity of deep-sea Photobacterium phosphoreum ANT-2200 - Sheng-Da Zhang; Claire-Lise Santini; Wei-Jia Zhang; Valérie Barbe; Sophie Mangenot; Charlotte Guyomar; Marc Garel; Hai-Tao Chen; Xue-Gong Li; Qun-Jian Yin; Yuan Zhao; Jean Armengaud; et al. (Extremophiles, 2016)

SIL1 Rescued Bip Elevation-Related Tau Hyperphosphorylation in ER Stress - Zan-Chao Liu; Jiang Chu; Li Lin; Jie Song; Lin-Na Ning; Hong-Bin Luo; Shu-Sheng Yang; Yan Shi; Qun Wang; Na Qu; Qi Zhang; Jian-Zhi Wang; et al. (Molecular Neurobiology, 2016)

Comprehensive analysis of NAC transcription factors in diploid Gossypium: sequence conservation and expression analysis uncover their roles during fiber development - Haihong Shang; Zhongna Wang; Changsong Zou; Zhen Zhang; Weijie Li; Junwen Li; Yuzhen Shi; Wankui Gong; Tingting Chen; Aiying Liu; Juwu Gong; Qun Ge; et al. (Science China Life Sciences, 2016)

Validating GWAS-Identified Risk Loci for Alzheimer’s Disease in Han Chinese Populations - Hui-Zhen Wang; Rui Bi; Qiu-Xiang Hu; Qun Xiang; Chen Zhang; Deng-Feng Zhang; Wen Zhang; Xiaohong Ma; Wanjun Guo; Wei Deng; Liansheng Zhao; Peiyan Ni; et al. (Molecular Neurobiology, 2016)

A novel Halomonas ventosae-specific virulent halovirus isolated from the Qiaohou salt mine in Yunnan, Southwest China - Chao-Qun Fu; Qin Zhao; Zhi-Ying Li; Yong-Xia Wang; Shi-Ying Zhang; Yong-Hong Lai; Wei Xiao; Xiao-Long Cui (Extremophiles, 2016)

Transcriptomic profiling revealed the regulatory mechanism of Arabidopsis seedlings response to oxidative stress from cryopreservation - Li Ren; Di Zhang; Guan-qun Chen; Barbara M. Reed; Xiao-hui Shen; Huo-ying Chen (Plant Cell Reports, 2015)

Aureoboletus formosus, a new bolete species from Hunan Province of China - Ming Zhang; Tai-Hui Li; Chao-Qun Wang; Bin Song; Jiang Xu (Mycological Progress, 2015)

Molecular mapping and markers for leaf rust resistance gene Lr24 in CIMMYT wheat line 19HRWSN-122 - Ai-yong Qi; Pei-pei Zhang; Xian-chun Xia; Zhong-hu He; Julio Huerta-Espino; Zai-feng Li; Da-qun Liu (Euphytica, 2015)

Occurrence of Polychlorodibenzothiophenes in Nanjing Section of the Yangtze River, China - Qun He; Li Qin; Xuesheng Zhang; Liansheng Wang; Ping Sun; Zunyao Wang (Archives of Environmental Contamination and Toxicology, 2015)

ROS-induced oxidative stress and apoptosis-like event directly affect the cell viability of cryopreserved embryogenic callus in Agapanthus praecox - Di Zhang; Li Ren; Guan-qun Chen; Jie Zhang; Barbara M. Reed; Xiao-hui Shen (Plant Cell Reports, 2015)

Identification and mapping of a novel blast resistance gene Pi57(t) in Oryza longistaminata - Peng Xu; Liying Dong; Jiawu Zhou; Jing Li; Yu Zhang; Fengyi Hu; Shufang Liu; Qun Wang; Wei Deng; Xianneng Deng; Didier Tharreau; Qinzhong Yang; et al. (Euphytica, 2015)

Expression and Functional Analysis of a Pathogenesis-Related Protein 1 Gene, TcLr19PR1, Involved in Wheat Resistance Against Leaf Rust Fungus - Lin Gao; Shen Wang; Xiao-Ying Li; Xue-Jun Wei; Yan-Jun Zhang; Hai-Yan Wang; Da-Qun Liu (Plant Molecular Biology Reporter, 2015)

A new alkaline lipase obtained from the metagenome of marine sponge Ircinia sp. - Jing Su; Fengli Zhang; Wei Sun; Valliappan Karuppiah; Guangya Zhang; Zhiyong Li; Qun Jiang (World Journal of Microbiology and Biotechnology, 2015)

Clipping alters the response of biomass production to experimental warming: A case study in an alpine meadow on the Tibetan Plateau, China - Gang Fu; Wei Sun; Cheng-Qun Yu; Xian-Zhou Zhang; Zhen-Xi Shen; Yun-Long Li; Peng-Wan Yang; Nan Zhou (Journal of Mountain Science, 2015)

Quantitative trait locus analysis and fine mapping of the qPL6 locus for panicle length in rice - Lin Zhang; Jianjun Wang; Junmin Wang; Linyou Wang; Bin Ma; Longjun Zeng; Yongbin Qi; Qun Li; Zuhua He (Theoretical and Applied Genetics, 2015)

MicroRNAs as Potential Biomarkers for Diagnosing Cancers of Central Nervous System: a Meta-analysis - Dong Wei; Qun Wan; Li Li; Haifeng Jin; Yonghong Liu; Yangang Wang; Guangyun Zhang (Molecular Neurobiology, 2015)

DLEC1, a 3p tumor suppressor, represses NF-κB signaling and is methylated in prostate cancer - Lian Zhang; Qian Zhang; LiLi Li; Zhaohui Wang; Jianming Ying; Yu Fan; Qun He; Tianjing LV; Wenke Han; Jun Li; Yang Yang; Ben Xu; et al. (Journal of Molecular Medicine, 2015)

Expression Analysis and Binding Assays in the Chemosensory Protein Gene Family Indicate Multiple Roles in Helicoverpa armigera - Zhao-Qun Li; Shuai Zhang; Jun-Yu Luo; Jing Zhu; Jin-Jie Cui; Shuang-Lin Dong (Journal of Chemical Ecology, 2015)

Pivoting neuromuscular control and proprioception in females and males - Song Joo Lee; Yupeng Ren; Sang Hoon Kang; François Geiger; Li-Qun Zhang (European Journal of Applied Physiology, 2015)

Cloning of a caffeoyl-coenzyme A O-methyltransferase from Camellia sinensis and analysis of its catalytic activity - Yue Zhang; Hai-peng Lv; Cheng-ying Ma; Li Guo; Jun-feng Tan; Qun-hua Peng; Zhi Lin (Journal of Zhejiang University-SCIENCE B, 2015)

Bacterial and archaeal community structures in the Arctic deep-sea sediment - Yan Li; Qun Liu; Chaolun Li; Yi Dong; Wenyan Zhang; Wuchang Zhang; Tian Xiao (Acta Oceanologica Sinica, 2015)

Nicotine-induced upregulation of VCAM-1, MMP-2, and MMP-9 through the α7-nAChR-JNK pathway in RAW264.7 and MOVAS cells - Zong-Zhuang Li; Zhen-Zhen Guo; Zhi Zhang; Qun-An Cao; Ya-Juan Zhu; Hua-Li Yao; Li-Li Wu; Qiu-Yan Dai (Molecular and Cellular Biochemistry, 2015)

The association between C-159T polymorphism in CD14 gene and susceptibility to tuberculosis: a meta-analysis - Qing Yuan; Huifang Chen; Xueyan Zheng; Xiaming Chen; Qun Li; Yanping Zhang; Xiaorong Zhang; Tingli Shi; Junhua Zhou; Qing Chen; Shouyi Yu (Molecular Biology Reports, 2014)

Two new truffles species, Tuber alboumbilicum and Tuber pseudobrumale from China - Shu-Hong Li; Lin-Yong Zheng; Cheng-Yi Liu; Yun Wang; Lin Li; Yong-Chang Zhao; Xiao-Lei Zhang; Mei Yang; Hai-Kuan Xiong; Yuan Qing; Li Wang; De-Qun Zhou (Mycological Progress, 2014)

Synthesis of novel spin-labeled podophyllotoxin derivatives as potential antineoplastic agents: Part XXV - Liu Yang; Xiang Nan; Wen-Qun Li; Mei-Juan Wang; Xiao-Bo Zhao; Ying-Qian Liu; Zhi-Jun Zhang; Kuo-Hsiung Lee (Medicinal Chemistry Research, 2014)

Identifying and Characterizing Resting State Networks in Temporally Dynamic Functional Connectomes - Xin Zhang; Xiang Li; Changfeng Jin; Hanbo Chen; Kaiming Li; Dajiang Zhu; Xi Jiang; Tuo Zhang; Jinglei Lv; Xintao Hu; Junwei Han; Qun Zhao; et al. (Brain Topography, 2014)

Catechin ameliorates cardiac dysfunction in rats with chronic heart failure by regulating the balance between Th17 and Treg cells - Qi Zhang; Li-qun Hu; Chang-sen Yin; Ping Chen; Hong-qi Li; Xin Sun; Guang Yan (Inflammation Research, 2014)

Dioxin and Dioxin-Like Compounds Suppress Acetylcholinesterase Activity via Transcriptional Downregulations In Vitro - Hai-Ming Xu; Heidi Qunhui Xie; Wu-Qun Tao; Zhi-Guang Zhou; Shuai-Zhang Li; Bin Zhao (Journal of Molecular Neuroscience, 2014)

Is right ventricular mid-septal pacing superior to apical pacing in patients with high degree atrio-ventricular block and moderately depressed left ventricular function? - Kang Chen; Ye Mao; Shao-hua Liu; Qiong Wu; Qing-zhi Luo; Wen-qi Pan; Qi Jin; Ning Zhang; Tian-you Ling; Ying Chen; Gang Gu; Wei-feng Shen; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Overexpression of leucine aminopeptidase 3 contributes to malignant development of human esophageal squamous cell carcinoma - Shu Zhang; Xiaojing Yang; Hui Shi; Mei Li; Qun Xue; Hanru Ren; Li Yao; Xueyu Chen; Jianguo Zhang; Huijie Wang (Journal of Molecular Histology, 2014)

Prevalence of human papillomavirus infection in esophageal and cervical cancers in the high incidence area for the two diseases from 2007 to 2009 in Linzhou of Henan Province, Northern China - Hong Yan Liu; Sheng Li Zhou; Jian Wei Ku; Dong Yun Zhang; Bei Li; Xue Na Han; Zong Min Fan; Ji Li Cui; Hong Li Lin; Er Tao Guo; Xi Chen; Yuan Yuan; et al. (Archives of Virology, 2014)

PI3K/Akt pathway involving into apoptosis and invasion in human colon cancer cells LoVo - Qun Guang Jiang; Tai Yuan Li; Dong Ning Liu; Hai Tao Zhang (Molecular Biology Reports, 2014)

High seroprevalence of Chlamydia infection in sows in Hunan province, subtropical China - Xiao-Xuan Zhang; Run-Cheng Li; Guo-Hua Liu; Wei Cong; Hui-Qun Song; Xing-Long Yu; Xing-Quan Zhu (Tropical Animal Health and Production, 2014)

Characterization of AvaR1, an autoregulator receptor that negatively controls avermectins production in a high avermectin-producing strain - Jian-Bo Wang; Feng Zhang; Jin-Yue Pu; Juan Zhao; Qun-Fei Zhao; Gong-Li Tang (Biotechnology Letters, 2014)

The effect of Se-deficient diet on gene expression of inflammatory cytokines in chicken brain - Peng-fei Sheng; Yue Jiang; Zi-wei Zhang; Jiu-li Zhang; Shu Li; Zi-qun Zhang; Shi-wen Xu (BioMetals, 2014)

Impacts of Urbanization and Station-relocation on Surface Air Temperature Series in Anhui Province, China - Yuan-Jian Yang; Bi-Wen Wu; Chun-e Shi; Jia-Hua Zhang; Yu-Bin Li; Wei-An Tang; Hua-Yang Wen; Hong-Qun Zhang; Tao Shi (Pure and Applied Geophysics, 2013)

Gender differences in offaxis neuromuscular control during stepping under a slippery condition - Song Joo Lee; Yupeng Ren; François Geiger; Li-Qun Zhang (European Journal of Applied Physiology, 2013)

Diffusion tensor imaging reveals evolution of primate brain architectures - Degang Zhang; Lei Guo; Dajiang Zhu; Kaiming Li; Longchuan Li; Hanbo Chen; Qun Zhao; Xiaoping Hu; Tianming Liu (Brain Structure and Function, 2013)

Quantification of Swelling and Erosion in the Controlled Release of a Poorly Water-Soluble Drug Using Synchrotron X-ray Computed Microtomography - Xianzhen Yin; Haiyan Li; Zhen Guo; Li Wu; Fangwei Chen; Marcel de Matas; Qun Shao; Tiqiao Xiao; Peter York; You He; Jiwen Zhang (The AAPS Journal, 2013)

Characterization of embryogenesis and early larval development in the Pacific triton, Charonia tritonis (Gastropoda: Caenogastropoda) - Lü-Ping Zhang; Jian-Jun Xia; Peng-Fei Peng; Hai-Peng Li; Peng Luo; Chao-Qun Hu (Invertebrate Reproduction & Development, 2013)

Comparison of the diversity of root-associated bacteria in Phragmites australis and Typha angustifolia L. in artificial wetlands - Yan Hong Li; Jing Nan Zhu; Qun Fang Liu; Yin Liu; Min Liu; Lei Liu; Qiang Zhang (World Journal of Microbiology and Biotechnology, 2013)

Effects of Cerium Oxide Nanoparticles on the Proliferation, Differentiation, and Mineralization Function of Primary Osteoblasts In Vitro - Guoqiang Zhou; Guangqi Gu; Yang Li; Qun Zhang; Wenying Wang; Shuxiang Wang; Jinchao Zhang (Biological Trace Element Research, 2013)

Response of ecosystem respiration to experimental warming and clipping at daily time scale in an alpine meadow of tibet - Gang Fu; Zhen-xi Shen; Xian-zhou Zhang; Cheng-qun Yu; Yu-ting Zhou; Yun-long Li; Peng-wan Yang (Journal of Mountain Science, 2013)

Selection of Antiviral Peptides Against Mink Enteritis Virus Using a Phage Display Peptide Library - Qingming Zhang; Yuping Wang; Qun Ji; Jingmin Gu; Shanshan Liu; Xin Feng; Changjiang Sun; Yingying Li; Liancheng Lei (Current Microbiology, 2013)

The Effects of Mn2+ on the Proliferation, Osteogenic Differentiation and Adipogenic Differentiation of Primary Mouse Bone Marrow Stromal Cells - Jinchao Zhang; Qun Zhang; Shenghui Li; Yingjian Hou; Haisong Zhang (Biological Trace Element Research, 2013)

Interaction of an anticyclonic eddy with sea ice in the western Arctic Ocean: an eddy-resolving model study - Qun Li; Zhanhai Zhang; Huiding Wu (Acta Oceanologica Sinica, 2013)

Identification of a canonical SCFSLF complex involved in S-RNase-based self-incompatibility of Pyrus (Rosaceae) - Chi Xu; Maofu Li; Junkai Wu; Han Guo; Qun Li; Yu’e Zhang; Jijie Chai; Tianzhong Li; Yongbiao Xue (Plant Molecular Biology, 2013)

Molecular phylogeography of Fagus engleriana (Fagaceae) in subtropical China: limited admixture among multiple refugia - Ming Lei; Qun Wang; Zhen-Jian Wu; Jordi López-Pujol; De-Zhu Li; Zhi-Yong Zhang (Tree Genetics & Genomes, 2012)

Greenhouse tomato–cucumber yield and soil N leaching as affected by reducing N rate and adding manure: a case study in the Yellow River Irrigation Region China - Ying Zhao; Jiang-Hang Luo; Xiao-Qun Chen; Xue-Jun Zhang; Wei-Li Zhang (Nutrient Cycling in Agroecosystems, 2012)

Land Banking: A Mechanism for Urban Sustainable Development in China - Qun Zhang; Wen Zhang; Manchun Li; Qiuhao Huang; Feixue Li (Ambio, 2012)

Knockout of fatty acid desaturase genes in Pichia pastoris GS115 and its effect on the fatty acid biosynthesis and physiological consequences - Ai-Qun Yu; Jian-Chun Zhu; Biao Zhang; Lai-Jun Xing; Ming-Chun Li (Archives of Microbiology, 2012)

Endothelin-induced differentiation of Nkx2.5+ cardiac progenitor cells into pacemaking cells - Xi Zhang; Jin-Ping Guo; Ya-Li Chi; Yan-Chun Liu; Chuan-Sen Zhang; Xiang-Qun Yang; Hai-Yan Lin; Er-Peng Jiang; Shao-Hu Xiong; Zhi-Ying Zhang; Bao-Hai Liu (Molecular and Cellular Biochemistry, 2012)

S-nitrosylation of c-Src via NMDAR-nNOS module promotes c-Src activation and NR2A phosphorylation in cerebral ischemia/reperfusion - Li-Juan Tang; Chong Li; Shu-Qun Hu; Yong-Ping Wu; Yan-Yan Zong; Chang-Cheng Sun; Fa Zhang; Guang-Yi Zhang (Molecular and Cellular Biochemistry, 2012)

De novo characterization of the antler tip of Chinese Sika deer transcriptome and analysis of gene expression related to rapid growth - Baojin Yao; Yu Zhao; Qun Wang; Mei Zhang; Meichen Liu; Hailong Liu; Juan Li (Molecular and Cellular Biochemistry, 2012)

Apolipoprotein A-I mimetic peptide D-4F promotes human endothelial progenitor cell proliferation, migration, adhesion though eNOS/NO pathway - Zhengang Zhang; Jianhua Qun; Chunmei Cao; Jun Wang; Wei Li; Yong Wu; Lin Du; Pei Zhao; Kaizheng Gong (Molecular Biology Reports, 2012)

Lowered Nudix type 5 (NUDT5) expression leads to cell cycle retardation in HeLa cells - Li-Qun Zhang; Da-Peng Dai; Wei Gan; Yasumitsu Takagi; Hiroshi Hayakawa; Mutsuo Sekiguchi; Jian-Ping Cai (Molecular and Cellular Biochemistry, 2012)

TNF-α Increases Bone Marrow Mesenchymal Stem Cell Migration to Ischemic Tissues - Qiong Xiao; Shi-kun Wang; Hua Tian; Li Xin; Zhi-geng Zou; Yan-lai Hu; Cui-ming Chang; Xue-ying Wang; Qun-sheng Yin; Xiang-hong Zhang; Li-yan Wang (Cell Biochemistry and Biophysics, 2012)

Effect of Different Intensity Pulsed Ultrasound on the Restoration of Rat Skeletal Muscle Contusion - Bin Shu; Zhijin Yang; Xiangping Li; Li-qun Zhang (Cell Biochemistry and Biophysics, 2012)

Increased cortico-subcortical functional connectivity in schizophrenia - Degang Zhang; Lei Guo; Xintao Hu; Kaiming Li; Qun Zhao; Tianming Liu (Brain Imaging and Behavior, 2012)

Mutations in exons of the CYP17-II gene affect sex steroid concentration in male Japanese flounder (Paralichthys olivaceus) - Ruiqin Ma; Feng He; Haishen Wen; Jifang Li; Bao Shi; Dan Shi; Miao Liu; Weijie Mu; Yuanqing Zhang; Jian Hu; Weiguo Han; Jianan Zhang; et al. (Journal of Ocean University of China, 2012)

Investigations on serviceability control of long-span structures under human-induced excitation - Xin Chen; Youliang Ding; Zhiqiang Zhang; Peng Sun; Ai-qun Li (Earthquake Engineering and Engineering Vibration, 2012)

Catalytic characteristics of plant-esterase from wheat flour - Chang-jun Hou; Kun He; Li-min Yang; Dan-qun Huo; Mei Yang; Shun Huang; Liang Zhang; Cai-hong Shen (World Journal of Microbiology and Biotechnology, 2012)

Current evidences on vascular endothelial growth factor polymorphisms and breast cancer susceptibility - Li-Xin Qiu; Ke Wang; Sheng Yang; Chen Mao; Lei Zhao; Lei Yao; Jian Zhang; Qun-Ling Zhang; Si Sun; Kai Xue (Molecular Biology Reports, 2011)

Observations of the Effect of Confined Space on Fluorescence and Diffusion Properties of Molecules in Single Conical Nanopore Channels - Li-Xiang Zhang; Xiao-Hong Cao; Wei-Peng Cai; Yao-Qun Li (Journal of Fluorescence, 2011)

Fenvalerate induces germ cell apoptosis in mouse testes through the Fas/FasL signaling pathway - Xian-Feng Zhao; Qun Wang; Yan-Li Ji; Hua Wang; Ping Liu; Cheng Zhang; Ying Zhang; De-Xiang Xu (Archives of Toxicology, 2011)

Dominant Contribution of Northern Chinese to the Paternal Genetic Structure of Chaoshanese in South China - Sheng-Ping Hu; Hui Li; Feng-Huan Zhang; Li-Qun Huang; Yan Lu (Biochemical Genetics, 2011)

Sex difference in QTc prolongation in chronic institutionalized patients with schizophrenia on long-term treatment with typical and atypical antipsychotics - Fu De Yang; Xiang Qun Wang; Xiu Ping Liu; Ke Xin Zhao; Wei Hong Fu; Xue Ru Hao; Xing Li Zhang; Guo Shu Huang; Sheng Cai Qu; Jing Shen Bai; Xu Feng Huang; Thomas R. Kosten; et al. (Psychopharmacology, 2011)

A high-throughput method for screening of Aspergillus niger mutants with high transglycosylation activity by detecting non-fermentable reducing sugar - Gui-guang Chen; Wei Li; Yun-kai Zhang; Yong-ling Qin; Kong-yang Wu; Zhi-qun Liang (World Journal of Microbiology and Biotechnology, 2011)

Differential Gene Expression Analysis of Yunnan Red Pear, Pyrus Pyrifolia, During Fruit Skin Coloration - Xiaodong Zhang; Andrew C Allan; Qiong Yi; Limei Chen; Kunzhi Li; Qun Shu; Jun Su (Plant Molecular Biology Reporter, 2011)

Earthquake characteristics and building damage in high-intensity areas of Wenchuan earthquake I: Yingxiu town - Chang-Rong He; Ru Zhang; Qun Chen; Sheng-Li Han (Natural Hazards, 2011)

Earthquake characteristics and building damage in high-intensity areas of Wenchuan earthquake II: Dujiangyan and Pengzhou City - Chang-Rong He; Qun Chen; Sheng-Li Han; Ru Zhang (Natural Hazards, 2011)

Effects of Different Carbon Sources on the Growth, Fatty Acids Production, and Expression of Three Desaturase Genes of Mortierella alpina ATCC 16266 - Ai-Qun Yu; Jian-Chun Zhu; Biao Zhang; Lai-Jun Xing; Mingchun Li (Current Microbiology, 2011)

Lack of association between methylenetetrahydrofolate reductase gene A1298C polymorphism and breast cancer susceptibility - Li-Xin Qiu; Jian Zhang; Wen-Hua Li; Qun-Ling Zhang; Hui Yu; Bi-Yun Wang; Lei-Ping Wang; Jia-Lei Wang; Hui-Jie Wang; Xiao-Jian Liu; Zhi-Guo Luo; Xiang-Hua Wu (Molecular Biology Reports, 2011)

The complete mitochondrial genomes of three cestode species of Taenia infecting animals and humans - Guo-Hua Liu; Rui-Qing Lin; Ming-Wei Li; Wei Liu; Yi Liu; Zi-Guo Yuan; Hui-Qun Song; Guang-Hui Zhao; Kou-Xing Zhang; Xing-Quan Zhu (Molecular Biology Reports, 2011)

Spatial prediction and analysis of Himalayan marmot plague natural epidemic foci in China based on HJ-1 satellite data - MengXu Gao; XiaoWen Li; ChunXiang Cao; Hao Zhang; Qun Li; Hang Zhou; QiSheng He; Min Xu; Jian Zhao; Sheng Zheng; Wei Chen (Science China Earth Sciences, 2010)

Influence of cell surface properties on adhesion ability of bifidobacteria - Li-Qun Wang; Xiang-Chen Meng; Bai-Rong Zhang; Yan Wang; Yu-Lin Shang (World Journal of Microbiology and Biotechnology, 2010)

Unique evolutionary pattern of numbers of gramineous NBS–LRR genes - Jing Li; Jing Ding; Wen Zhang; Yuanli Zhang; Ping Tang; Jian-Qun Chen; Dacheng Tian; Sihai Yang (Molecular Genetics and Genomics, 2010)

Characterization of DUF724 gene family in Arabidopsis thaliana - Xi Cao; Ke-Zhen Yang; Chuan Xia; Xue-Qin Zhang; Li-Qun Chen; De Ye (Plant Molecular Biology, 2010)

Porphyrin and Galactosyl Conjugated Micelles for Targeting Photodynamic Therapy - De-Qun Wu; Ze-Yong Li; Cao Li; Jian-Jun Fan; Bo Lu; Cong Chang; Si-Xue Cheng; Xian-Zheng Zhang; Ren-Xi Zhuo (Pharmaceutical Research, 2010)

Effect of temperature on phytoextraction of hexavalent and trivalent chromium by hybrid willows - Xiao-Zhang Yu; Xiao-Ying Peng; Li-Qun Xing (Ecotoxicology, 2010)

Erratum to: Cypermethrin exposure during puberty disrupts testosterone synthesis via downregulating StAR in mouse testes - Hua Wang; Qun Wang; Xian-Feng Zhao; Ping Liu; Xiu-Hong Meng; Tao Yu; Yan-Li Ji; Heng Zhang; Cheng Zhang; Ying Zhang; De-Xiang Xu (Archives of Toxicology, 2010)

Cypermethrin exposure during puberty disrupts testosterone synthesis via downregulating StAR in mouse testes - Hua Wang; Qun Wang; Xian-Feng Zhao; Ping Liu; Xiu-Hong Meng; Tao Yu; Yan-Li Ji; Heng Zhang; Cheng Zhang; Ying Zhang; De-Xiang Xu (Archives of Toxicology, 2010)

The Influence of Cosolvent on the Complexation of HP-β-cyclodextrins with Oleanolic Acid and Ursolic Acid - Rui Li; Peng Quan; Dong-Fei Liu; Fang-Di Wei; Qing Zhang; Qun-Wei Xu (AAPS PharmSciTech, 2009)

Serum Zinc, Copper, and Zinc/Copper in Healthy Residents of Jinan - Hong-qun Zhang; Ning Li; Zheng Zhang; Shan Gao; Hong-yin Yin; Dong-mei Guo; Xibao Gao (Biological Trace Element Research, 2009)

Genetic features of a pollen-part mutation suggest an inhibitory role for the Antirrhinum pollen self-incompatibility determinant - Yongbiao Xue; Yijing Zhang; Qiuying Yang; Qun Li; Zhukuan Cheng; Hugh G. Dickinson (Plant Molecular Biology, 2009)

Microprojectile bombardment of Laminaria japonica gametophytes and rapid propagation of transgenic lines within a bubble-column bioreactor - Xiangyuan Deng; Song Qin; Qun Zhang; Peng Jiang; Yulin Cui; Xiaokun Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2009)

Oxidative damage increased in presenilin1/presenilin2 conditional double knockout mice - Dong-Li Zhang; Yi-Qun Chen; Xu Jiang; Ting-Ting Ji; Bing Mei (Neuroscience Bulletin, 2009)

Functional Annotation and Analysis of Expressed Sequence Tags from the Hepatopancreas of Mitten Crab (Eriocheir sinensis) - Hui Jiang; Yi-Mei Cai; Li-Qiao Chen; Xiao-Wei Zhang; Song-Nian Hu; Qun Wang (Marine Biotechnology, 2009)

Effect of the untranslated region and signal peptide sequence of the insecticidal gene from Pseudomonas pseudoalcaligenes on the activity of its expression products in tobacco - Min Huang; Da-Xu Li; Wen-Liang Xiang; Hao Chen; Jian-Hua Guo; Jian Zhao; Jie Zhang; Zhi-Rong Yang; Qun Sun (World Journal of Microbiology and Biotechnology, 2009)

The correlations between HPV16 infection and expressions of c-erbB-2 and bcl-2 in breast carcinoma - Qian He; Shu-Qun Zhang; Yong-Lie Chu; Xiao-Li Jia; Xiang-Ling Wang (Molecular Biology Reports, 2009)

Characterization of a putative pollen-specific arabinogalactan protein gene, BcMF8, from Brassica campestris ssp. chinensis - Li Huang; Jia-Shu Cao; Ai-Hong Zhang; Yi-Qun Ye (Molecular Biology Reports, 2008)

Differences in uptake and translocation of hexavalent and trivalent chromium by two species of willows - Xiao-Zhang Yu; Ji-Dong Gu; Li-Qun Xing (Ecotoxicology, 2008)

The quorum-sensing system AvsR-AvsI regulates both long-chain and short-chain acyl-homoserine lactones in Agrobacterium vitis E26 - Yuan-Hong Wang; Li-Qun Zhang; Jin-Yun Li; Jian-Hui Wang; Hui-Min Wang (Antonie van Leeuwenhoek, 2008)

T1 locus in cotton is the candidate gene affecting lint percentage, fiber quality and spiny bollworm (Earias spp.) resistance - Qun Wan; Zhengsheng Zhang; Meichun Hu; Li Chen; Dajun Liu; Xiao Chen; Wei Wang; Jing Zheng (Euphytica, 2007)

Use of a novel multiplex probe array for rapid identification of Mycobacterium species from clinical isolates - Shu-Lin Zhang; Jian-Guo Shen; Gwan-Han Shen; Zhan-Qiang Sun; Ping-Hui Xu; Yi-Li Peng; Zhi-Rong Yang; Qun Sun (World Journal of Microbiology and Biotechnology, 2007)

Agrobacterium–mediated genetic transformation of Elymus breviaristatus with Pseudomonas pseudoalcaligenes insecticidal protein gene - Daxu Li; Qun Sun; Min Huang; Jie Zhang; Shiqie Bai; Linyong Zheng; Jian Zhao; Dunlian Qiu; Li Li; Zhirong Yang; Minghong You; Gang Liu; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2007)

Genotypic Analysis of Multidrug-Resistant Mycobacterium tuberculosis Isolates Recovered From Central China - Shu-Lin Zhang; Hua Qi; Dun-Lian Qiu; Da-Xu Li; Jie Zhang; Chang-Mei Du; Guo-Bin Wang; Zhi-Rong Yang; Qun Sun (Biochemical Genetics, 2007)

Quorum-sensing system influences root colonization and biological control ability in Pseudomonas fluorescens 2P24 - Hai-Lei Wei; Li-Qun Zhang (Antonie van Leeuwenhoek, 2006)

Conversion of an obligate autotrophic bacteria to heterotrophic growth: expression of a heterogeneous phosphofructokinase gene in the chemolithotroph Acidithiobacillus thiooxidans - Ke Li Tian; Jian Qun Lin; Xiang Mei Liu; Ying Liu; Chang Kai Zhang; Wang Ming Yan (Biotechnology Letters, 2003)

Research on disturbed mechanism of thermal noises of the surface in abrupt geothermal anomaly - Li-qun Bo; Xin-liang Xu; Ren-kui Hua; Xue-xia Zhang (Chinese Geographical Science, 2001)

Accumulation of uranium at low concentration by the green alga Scenedesmus obliquus 34 - Xiaozhi Zhang; Shanggeng Luo; Qun Yang; Huaili Zhang; Jinying Li (Journal of Applied Phycology, 1997)